Adhesive film and adhesive composite sheet

By developing curable adhesive film and adhesive composite sheet, the operation difficulties and bonding problems of large-scale glass plates in the sensor are solved, effective transmission suppression of light in a specific wavelength range and firm bonding of glass are achieved, and suitable for sensors Protect.

CN112778917BActive Publication Date: 2024-12-20LINTEC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011136842.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-08
Filing Date
2020-10-22
Publication Date
2024-12-20
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

In the prior art, the colored glass plate used to suppress light transmission in a specific wavelength range has problems of operational difficulties and easy rupture in large-scale production, and the disclosed adhesive sheet cannot be used directly to prevent sensor failure.

Method used

A curable adhesive film has been developed, which has a linear transmittance of 70% or more to 800 nm to 1400 nm light, a linear transmittance of 850 nm light, and a linear transmittance of 400 nm light, and a linear transmittance of 40% or less to 40%, and passes through The bonding of the adhesive film to the glass forms a new type of adhesive composite sheet suitable for use in the sensor.

Benefits of technology

The sensor is effectively suppressed from light transmission in the wavelength range outside the detection object, improves the adhesion of the glass, and a device that suppresses the transmission of visible light outside is stably constructed, which is suitable for sensors with cover glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112778917B_ABST
    Figure CN112778917B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive film, which is used to bond two plates to each other and is curable, wherein the linear transmittance of the two plates to light with a wavelength of 800nm ​​to 1400nm is 70% or more, the linear transmittance of the cured product of the adhesive film to light with a wavelength of 850nm is 60% or more, and the linear transmittance of the cured product to light with a wavelength of 400nm is 40% or less, and the shear strength of the test piece having a cured product of the adhesive film with a size of 2mm×2mm and a thickness of 20μm, a first glass sheet with a thickness of 900μm disposed on the entire surface of one surface of the cured product, and a second glass sheet with a thickness of 350μm disposed on the entire surface of the other surface of the cured product is 5MPa or more. The present invention also provides an adhesive composite sheet, which has a support sheet and the adhesive film on one surface of the support sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive film and an adhesive composite sheet.

[0002] The present invention claims priority based on Japanese Patent Application No. 2019-203084 filed in Japan on November 8, 2019, the contents of which are incorporated herein by reference. Background Art

[0003] In an electronic device, the sensor is fixed on a substrate, for example, and one side of the light receiving part is protected by a cover glass. In addition, in order to prevent light in a specific wavelength range other than the target from reaching the light receiving part of the sensor, a device for suppressing the transmission of light in such a specific wavelength range is provided between the cover glass and the sensor. This is to make the sensor detect light in the target wavelength range and prevent the sensor from malfunctioning due to light in a wavelength range other than the target. For example, when the sensor detects infrared rays, visible light can be listed as a typical light in a wavelength range other than the target.

[0004] In order to suppress the transmission of light in a specific wavelength range, a glass plate colored by coating or vapor-depositing a colorant on its surface may be fixed with an adhesive and arranged on the surface of the sensor on the light receiving part side. In this case, the cover glass is separately fixed to the glass plate with an adhesive.

[0005] However, it is difficult to increase the scale of production of such colored glass plates because large glass plates are prone to warping and further cracking, making their handling difficult.

[0006] Therefore, a device that can replace such a colored glass plate is sought. For example, a resin film that suppresses the transmission of light in a specific wavelength range can solve the above-mentioned drawbacks, and an adhesive resin film (adhesive film) is particularly suitable.

[0007] As such an adhesive film (adhesive sheet) for suppressing the transmission of light, an adhesive film (adhesive sheet) used for manufacturing semiconductor devices is known so far. In addition, as such an adhesive sheet, for example, an adhesive sheet is disclosed, which contains a pigment that absorbs or reflects light in the wavelength range of 290nm to 450nm, and the linear transmittance of the light in the wavelength range of 290nm to 450nm is 40% or less (see Patent Document 1).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 4975564 Summary of the invention

[0011] Technical Problems to be Solved by the Invention

[0012] However, the adhesive sheet disclosed in Patent Document 1 is intended to identify itself without using a sensor or the like, and cannot be used directly for the purpose of preventing a malfunction of a sensor.

[0013] An object of the present invention is to provide a novel adhesive film suitable for suppressing the transmission of light in a wavelength range other than a detection target in a sensor having a cover glass, and an adhesive composite sheet having the adhesive film.

[0014] Technical means to solve technical problems

[0015] The present invention provides an adhesive film, which is a curable adhesive film, and the adhesive film is used to bond two plates to each other, the two plates have a linear transmittance of 70% or more to light with a wavelength of 800nm ​​to 1400nm, the cured product of the adhesive film has a linear transmittance of 60% or more to light with a wavelength of 850nm, and the cured product of the adhesive film has a linear transmittance of 40% or less to light with a wavelength of 400nm, and a cured product of the adhesive film having a size of 2mm×2mm and a thickness of 20μm is prepared, and a thickness of 100μm is provided on the entire surface of one surface of the cured product. A test piece is provided which comprises a first glass piece with a thickness of 900 μm and a second glass piece with a thickness of 350 μm provided on the entire surface of the other surface of the cured object, and is formed by aligning the side surface of the cured object with the side surface of the second glass piece; when force is applied simultaneously to the aligned portion of the side surface of the cured object and the side surface of the second glass piece in the test piece at a speed of 200 μm / s in a direction parallel to one surface of the cured object, the maximum value of the force applied until the cured object is broken or peeled off from the first glass piece is 5 MPa or more.

[0016] The additionally heated product obtained by heating the cured product of the adhesive film of the present invention at 175° C. for 5 hours may have a linear transmittance of 50% or more for light having a wavelength of 850 nm.

[0017] The present invention provides an adhesive composite sheet, which comprises a support sheet and the adhesive film on one surface of the support sheet.

[0018] In the adhesive composite sheet of the present invention, the support sheet includes a substrate and an adhesive layer provided on one surface of the substrate, and the adhesive layer may be disposed between the substrate and the adhesive film.

[0019] Effects of the Invention

[0020] According to the present invention, it is possible to provide a novel adhesive film suitable for suppressing the transmission of light in a wavelength range other than a detection target in a sensor having a cover glass, and an adhesive composite sheet having the adhesive film. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a cross-sectional view schematically showing an adhesive film according to one embodiment of the present invention.

[0022] Figure 2 This is a cross-sectional view for schematically illustrating a method for measuring the shear strength of a cured product of an adhesive film according to an embodiment of the present invention.

[0023] Figure 3 This is a cross-sectional view schematically showing an example of a pressure-sensitive adhesive composite sheet according to an embodiment of the present invention.

[0024] Figure 4 This is a cross-sectional view schematically showing another example of the adhesive composite sheet according to one embodiment of the present invention.

[0025] Description of Reference Numerals

[0026] 101, 102: adhesive composite sheet; 10, 20: support sheet; 10a, 20a: one side (first side) of the support sheet; 11: substrate; 11a: one side (first side) of the substrate; 12: adhesive layer; 13: adhesive film; 13a: one side (first side) of the adhesive film; 13b: the other side (second side) of the adhesive film; 90: cured product of the adhesive film; 90a: one side (first side) of the cured product of the adhesive film; 90b: the other side (second side) of the cured product of the adhesive film; 90c: the side surface of the cured product of the adhesive film; 91: first glass sheet; 92: second glass sheet; 92c: the side surface of the second glass sheet; 9: test piece. DETAILED DESCRIPTION

[0027] ◇Adhesive film

[0028] An adhesive film according to one embodiment of the present invention is a curable adhesive film, which is used to bond two plates to each other, wherein the linear transmittance of the two plates to light with a wavelength of 800nm ​​to 1400nm (sometimes abbreviated as "light (800nm ​​to 1400nm)" in this specification) is 70% or more, the linear transmittance of the cured product of the adhesive film to light with a wavelength of 850nm (sometimes abbreviated as "light (850nm)" in this specification) is 60% or more, and the linear transmittance of the cured product of the adhesive film to light with a wavelength of 400nm (sometimes abbreviated as "light (400nm)" in this specification) is 40% or less, and a 2mm×2mm-sized and 20μ thick adhesive film is prepared. m, a first glass sheet with a thickness of 900 μm and provided on the entire surface of one surface of the cured product, and a second glass sheet with a thickness of 350 μm and provided on the entire surface of the other surface of the cured product, and a test piece formed by aligning the side surface of the cured product with the side surface of the second glass sheet, when a force is simultaneously applied to the aligned portion of the side surface of the cured product and the side surface of the second glass sheet in the test piece at a speed of 200 μm / s along a direction parallel to one surface of the cured product, the maximum value of the force applied until the cured product is broken or the cured product is peeled off from the first glass sheet (sometimes abbreviated as "shear strength" in this specification) is 5 MPa or more.

[0029] The adhesive film of this embodiment can be used to bond glasses together, and the cured product of the adhesive film can bond these glasses together more firmly.

[0030] For example, the adhesive film of this embodiment is suitably applied to a sensor having a cover glass.

[0031] More specifically, a glass plate (hereinafter sometimes referred to as an "inner glass plate") can be arranged on the surface of the light receiving part side of the sensor via a certain fixing method such as an adhesive or a sticky agent different from the adhesive film of the present embodiment, and the adhesive film is set between the surface of the inner glass plate opposite to the sensor side and the cover glass.

[0032] The adhesive film of this embodiment is used to bond two plates with a light (800nm ​​to 1400nm) linear transmittance of 70% or more. Here, "light (800nm ​​to 1400nm) linear transmittance of 70% or more" means "the linear transmittance of light in at least a part of the wavelength range of 800nm ​​to 1400nm is 70% or more", and may also be "the linear transmittance of light in the entire wavelength range of 800nm ​​to 1400nm is 70% or more". Therefore, for example, as the cover glass and the inner glass plate, a cover glass and an inner glass plate having such a light (800nm ​​to 1400nm) linear transmittance may be used.

[0033] The adhesive film and its cured product of the present embodiment have specific properties related to light transmission, and bond glasses (for example, cover glass and inner glass plate) to each other. In addition, the cured product of the adhesive film bonds glasses to each other more firmly.

[0034] The cured product of the adhesive film of this embodiment has a linear transmittance of 60% or more for light (850 nm) and a high linear transmittance for infrared rays, but has a linear transmittance of 40% or less for light (400 nm) and a low linear transmittance for visible light.

[0035] Furthermore, the shear strength of the cured product of the adhesive film of the present embodiment is 5 MPa or more, and the adhesive force to glass is high.

[0036] By configuring the cured product of the adhesive film on the sensor as described above, the following device can be stably constructed: when light is incident on the sensor from the outside of the cover glass side, infrared light that is the detection object of the sensor is transmitted, and the transmission of visible light outside the detection object (outside the target) is suppressed.

[0037] In addition, the above-mentioned "Japanese Patent Gazette No. 4975564" (Patent Document 1) discloses "the linear transmittance of the adhesive sheet used for semiconductor device manufacturing for light in the wavelength range of 290nm to 450nm", but it cannot be concluded that the adhesive sheet is a cured product of the curable sheet, and it does not make any suggestion about the cured product of the adhesive film of this embodiment.

[0038] The adhesive film of the present embodiment can be used for a desired purpose by, for example, using it together with a support sheet described later to form an adhesive composite sheet, and by attaching the adhesive composite sheet to an object.

[0039] In addition, the adhesive film of this embodiment can be attached to an object without being used together with a support sheet, and then further attached to a support sheet to form an adhesive composite sheet, or by attaching a dicing sheet described later to form a dicing / diebonding sheet, and can be used for the target purpose in any of the above states.

[0040] When one of the above-mentioned glasses (for example, one of the cover glass and the inner glass plate) corresponds to a glass chip obtained by dividing a glass such as a glass wafer, the adhesive composite sheet or the diced solid sheet can be used to prepare a laminate of the glass and the adhesive film (sometimes referred to as a "glass chip with an adhesive film" in this specification). The manufacturing method thereof will be described separately later.

[0041] Figure 1In order to make it easier to understand the features of the present invention, important parts of the drawings used in the following description are sometimes enlarged for convenience, and the dimensional ratios of the components are not necessarily the same as the actual ones.

[0042] The adhesive film 13 shown here has a first release film 151 on one surface 13a thereof (sometimes referred to as the "first surface" in this specification), and has a second release film 152 on the other surface 13b (sometimes referred to as the "second surface" in this specification) which is opposite to the first surface 13a.

[0043] Such an adhesive film 13 is preferably stored in a roll shape, for example.

[0044] The cured product of the adhesive film 13 has a light (850 nm) linear transmittance of 60% or more and a light (400 nm) linear transmittance of 40% or less.

[0045] The shear strength of the cured product of the adhesive film 13 is 5 MPa or more.

[0046] Both the first release film 151 and the second release film 152 may be known release films.

[0047] The first release film 151 and the second release film 152 may be identical to each other, or may be different release films having different release forces required when being released from the pressure-sensitive adhesive film 13 .

[0048] exist Figure 1 In the adhesive film 13 shown, one exposed surface produced by removing both the first release film 151 and the second release film 152 becomes the surface attached to the cover glass, and the other exposed surface becomes the surface attached to the inner glass plate. For example, when the first surface 13a is the surface attached to the cover glass, the second surface 13b becomes the surface attached to the inner glass plate.

[0049] exist Figure 1 , an example is shown in which a release film is provided on both sides (the first side 13a and the second side 13b) of the adhesive film 13, however, the release film may be provided on only one side of the adhesive film 13, that is, the release film may be provided only on the first side 13a or only on the second side 13b.

[0050] 《Linear transmittance of light (850nm) of cured adhesive film》

[0051] The light (850nm) linear transmittance of the cured product of the adhesive film may be 60% or more. From the point of view of making the linear transmittance of the cured product to infrared rays higher, the light (850nm) linear transmittance of the cured product is preferably 63% or more, more preferably 66% or more, for example, any range of 70% or more and 75% or more.

[0052] The upper limit of the linear transmittance of light (850 nm) of the cured product of the adhesive film is not particularly limited. That is, the linear transmittance of light (850 nm) may be 100% or less.

[0053] The light (850nm) linear transmittance of the cured product of the adhesive film can be appropriately adjusted within the range set by any combination of the above lower limit and upper limit. For example, in one embodiment, the light (850nm) linear transmittance is preferably 60-100%, more preferably 63-100%, further preferably 66-100%, and can also be any range of 70-100% and 75-100%. However, the above range is only an example of the light (850nm) linear transmittance of the cured product of the adhesive film.

[0054] 《Linear transmittance of light (overall range of 800nm ​​to 1400nm) of cured adhesive film》

[0055] The cured product of the adhesive film preferably has a linear transmittance of 60% or more for light in the entire wavelength range of 800nm ​​to 1400nm, and may also be in the same numerical range (lower limit, upper limit) as the linear transmittance of the cured product of the adhesive film for light (850nm) described above. The adhesive film having such characteristics can be used as a sensor for detecting infrared rays in a wide range of fields.

[0056] 《Linear transmittance of light (850nm) of adhesive film》

[0057] The linear transmittance of light (850 nm) of the adhesive film is not particularly limited as long as the linear transmittance of light (850 nm) of the cured product of the adhesive film described above can be achieved.

[0058] For example, the linear transmittance of light (850 nm) of the adhesive film is 100% or less, and may be any range of 60% or more, 63% or more, 66% or more, 70% or more, 75% or more, and 80% or more, or any range of 60-100%, 63-100%, 66-100%, 70-100%, 75-100%, and 80-100%. However, these ranges are only examples of the linear transmittance of light (850 nm) of the adhesive film.

[0059] 《Linear transmittance of light (400nm) of cured adhesive film》

[0060] The light (400nm) linear transmittance of the cured product of the adhesive film may be 40% or less. From the point of view of making the linear transmittance of the cured product to visible light lower, the light (400nm) linear transmittance of the cured product is preferably 37% or less, more preferably 34% or less, for example, it can be any range of 30% or less and 20% or less.

[0061] The lower limit of the linear transmittance of light (400 nm) of the cured product of the adhesive film is not particularly limited. That is, the linear transmittance of light (400 nm) may be 0% or more.

[0062] The light (400nm) linear transmittance of the cured product of the adhesive film can be appropriately adjusted within the range set by any combination of the above lower limit and any upper limit. For example, in one embodiment, the light (400nm) linear transmittance is preferably 0 to 40%, more preferably 0 to 37%, further preferably 0 to 34%, and can also be any range of 0 to 30% and 0 to 20. However, the above range is only an example of the light (400nm) linear transmittance of the cured product of the adhesive film.

[0063] 《Linear transmittance of light (400nm) of adhesive film》

[0064] The linear transmittance of light (400 nm) of the adhesive film is not particularly limited as long as the linear transmittance of light (400 nm) of the cured product of the adhesive film described above can be achieved.

[0065] For example, the linear transmittance of light (400 nm) of the adhesive film is 0% or more, and may be any range of 45% or less, 40% or less, 37% or less, 34% or less, 30% or less, and 20% or less, or any range of 0 to 45%, 0 to 40%, 0 to 37%, 0 to 34%, 0 to 30%, and 0 to 20%. However, the above range is only an example of the linear transmittance of light (400 nm) of the adhesive film.

[0066] The adhesive film has curability, and may be either thermosetting or energy-ray curing, or may have both thermosetting and energy-ray curing properties. When the adhesive film has both thermosetting and energy-ray curing properties, when the contribution of thermal curing to the curing of the adhesive film is greater than the contribution of energy-ray curing, the adhesive film is regarded as a thermosetting adhesive film. On the contrary, when the contribution of energy-ray curing to the curing of the adhesive film is greater than the contribution of thermal curing, the adhesive film is regarded as an energy-ray curing adhesive film. For example, when the adhesive film is cured by heating the adhesive film without irradiating the adhesive film with energy rays, the adhesive film is regarded as a thermosetting adhesive film.

[0067] In this specification, "energy ray" refers to an energy ray having an energy quantum in an electromagnetic wave or a charged particle beam. Examples of energy ray include ultraviolet rays, radiation, electron beams, etc. For example, ultraviolet rays can be irradiated by using a high-pressure mercury lamp, a fusion lamp, a xenon lamp, a black light lamp, or an LED lamp as an ultraviolet source. As an electron beam, an electron beam generated by an electron beam accelerator, etc. can be irradiated.

[0068] In this specification, "energy ray-curable" means a property of being cured by irradiation with energy rays.

[0069] In this embodiment, the cured product of the adhesive film for which the linear transmittance of light (850 nm) and the linear transmittance of light (400 nm) are specified is: a thermosetting adhesive film obtained by heating it at 160° C. for 1 hour; or 2 , light intensity is 200mJ / cm 2 An energy ray cured product obtained by irradiating an energy ray curable adhesive film with energy rays under conditions of.

[0070] When the cured product of the adhesive film is actually used, the curing conditions when the adhesive film is cured to form the cured product are not particularly limited as long as the degree of curing of the cured product is sufficiently increased, and may be appropriately selected according to the type of the adhesive film.

[0071] The heating temperature during heat curing of the thermosetting adhesive film is preferably 100 to 200° C., for example, it may be any range of 125 to 185° C. and 150 to 170° C. Furthermore, the heating time during heat curing is preferably 0.5 to 5 hours, for example, it may be any range of 0.5 to 4 hours and 0.5 to 3 hours.

[0072] The irradiance of the energy ray when the energy ray-curable adhesive film is cured by energy ray is preferably 60 to 320 mW / cm 2Furthermore, the amount of energy ray during the energy ray curing is preferably 100 to 1000 mJ / cm 2 .

[0073] 《Linear transmittance of light (850nm) of the additionally heated cured product of the adhesive film》

[0074] The linear transmittance of light (850 nm) of the additional heated product (sometimes simply referred to as "additional heated product" in this specification) obtained by further heating the cured product of the adhesive film at 175° C. for 5 hours is not particularly limited. From the viewpoint that the cured product can maintain a high linear transmittance of infrared rays for a longer period of time during actual use and has higher practicality, the linear transmittance of light (850 nm) of the additional heated product is preferably 50% or more, more preferably 60% or more, and further preferably 65% ​​or more, for example, it can be any range of 70% or more and 75% or more.

[0075] The upper limit of the linear transmittance of the additionally heated object at 850 nm is not particularly limited. That is, the linear transmittance of the additionally heated object at 850 nm may be 100% or less, and may be 90% or less, for example.

[0076] The linear transmittance of light (850nm) of the additional heated object can be appropriately adjusted within the range set by any combination of any of the above lower limits and any of the upper limits. For example, in one embodiment, the linear transmittance of light (850nm) is preferably 50-100%, more preferably 60-100%, further preferably 65-100%, and can also be any range of 70-100% and 75-100%. However, the above range is only an example of the linear transmittance of light (850nm) of the additional heated object.

[0077] The properties related to light transmission of the cured adhesive film, such as the linear transmittance of light (850 nm) and the linear transmittance of light (400 nm), and the properties related to light transmission of the adhesive film, such as the linear transmittance of light (850 nm) and the linear transmittance of light (400 nm), and the properties related to light transmission of the additional heated object, such as the linear transmittance of light (850 nm) of the additional heated object, can be adjusted by adjusting the type or content of the components contained in the adhesive film, or the thickness of the adhesive film, etc. In particular, the above-mentioned properties related to light transmission can be adjusted in a wider range by adjusting whether the adhesive film contains a colorant (for example, the colorant (I) described later), the type or content of the colorant when the colorant is contained, or whether the adhesive film contains a filler (for example, the filler (d) described later), and the type (for example, material, average particle size, etc.) or content of the filler when the filler is contained.

[0078] 《Shear strength of cured adhesive film》

[0079] Figure 2 This is a cross-sectional view for schematically illustrating the method for measuring the shear strength of the cured product of the adhesive film.

[0080] In addition, Figure 2 In the following drawings, the same components as those shown in the drawings that have been described are denoted by the same reference numerals as those in the drawings that have been described, and detailed description thereof will be omitted.

[0081] When measuring the shear strength, a test piece 9 was prepared.

[0082] The test piece 9 includes a cured product 90 having an adhesive film, a second glass sheet 92 provided on the entire first surface 90 a of the cured product 90 , and a first glass sheet 91 provided on the entire second surface 90 b of the cured product 90 .

[0083] The cured product 90 of the adhesive film is a cured product of the adhesive film of the present embodiment.

[0084] The planar shapes of the first surface 90 a and the second surface 90 b of the cured product 90 are rectangular (square).

[0085] The size of the solidified material 90 (the size of the first surface 90 a and the second surface 90 b ) is 2 mm×2 mm, and the thickness of the solidified material 90 is 20 μm.

[0086] The thickness of the first glass sheet 91 is 900 μm, and the thickness of the second glass sheet 92 is 350 μm.

[0087] In the test piece 9, the side 90c of the cured product 90 of the adhesive film is aligned with the side 92c of the second glass sheet 92. For example, in the cross section, in a direction parallel to the first surface 90a or the second surface 90b of the adhesive film 90, the position of the side 90c of the adhesive film 90 is consistent with the position of the side 92c of the second glass sheet 92.

[0088] It is preferable that at least a portion of the side surface 92c of the second glass sheet 92 that is aligned with the side surface 90c of the cured product 90 of the adhesive film is a flat surface.

[0089] The size of the contact surface of the second glass sheet 92 with the cured object 90 may be greater than or equal to the size of the first surface 90 a of the cured object 90 , or may be the same as the first surface 90 a of the cured object 90 .

[0090] The planar shape of the contact surface of the second glass sheet 92 with the cured object 90 is preferably rectangular, for example, may be square. The planar shape of the contact surface of the second glass sheet 92 with the cured object 90 is preferably the same as the planar shape of the first surface 90a of the cured object 90.

[0091] As described in the embodiments below, when the cured object 90 is formed by cutting and curing an adhesive film (not shown in the figure), and the second glass sheet 92 is formed by splitting a glass sheet (not shown in the figure), the above-mentioned cutting and splitting processes can be performed simultaneously. In this case, the contact surface of the second glass sheet 92 with the cured object 90 and the first surface 90a of the cured object 90 can be made to be the same size and the same shape as each other, and the side surface 90c of the cured object 90 and the side surface 92c of the second glass sheet 92 can also be aligned relatively easily.

[0092] The size of the contact surface of the first glass sheet 91 with the cured product 90 of the adhesive film can be greater than or equal to the size of the second surface 90b of the cured product 90. Preferably, the size of the contact surface of the first glass sheet 91 with the cured product 90 of the adhesive film is greater than the size of the second surface 90b of the cured product 90.

[0093] The planar shape of the surface of the first glass sheet 91 in contact with the cured object 90 is not particularly limited as long as the first glass sheet 91 can cover the entire second surface 90 b of the cured object 90 , and may be, for example, a rectangular shape.

[0094] When measuring the shear strength, a force P is simultaneously applied at a speed of 200 μm / s to the aligned portion of the side surface 90c of the cured product 90 of the adhesive film in the test piece 9 and the side surface 92c of the second glass sheet 92 in a direction parallel to one surface (the first surface 90a or the second surface 90b) of the cured product 90. Here, a case where the force P is applied to the aligned portion using the pressing device 8 is shown.

[0095] From the viewpoint of being able to measure the shear strength with higher accuracy, the portion where the force is applied by the pressing device 8 is preferably a flat surface, and the pressing device 8 is more preferably in the form of a plate.

[0096] Examples of the constituent material of the extrusion device 8 include metals and the like.

[0097] As described above, it is preferable that the pressing device 8 does not come into contact with the first glass sheet 91 when the force P is applied simultaneously to the cured product 90 of the adhesive film and the second glass sheet 92 .

[0098] As described above, in this embodiment, a force P is applied to the aligned portion between the side surface 90c of the cured product 90 of the adhesive film and the side surface 92c of the second glass sheet 92, and the maximum value of the force P applied until the cured product 90 is broken or the cured product 90 is peeled off from the first glass sheet 91 is used as the shear strength of the cured product 90.

[0099] The test piece (for example, test piece 9) to be measured for the shear strength is included in a target object (that is, a laminated structure having a structure in which glass is laminated on both surfaces of a cured product of an adhesive film) that is assumed when the adhesive film is actually used.

[0100] The shear strength of the cured product of the adhesive film may be 5 MPa or more. From the perspective of making the adhesive film and its cured product have higher adhesion to glass, the shear strength of the adhesive film may be any range of 10 MPa or more, 15 MPa or more, 20 MPa or more, 30 MPa or more, and 40 MPa or more.

[0101] The upper limit of the shear strength of the cured product of the adhesive film is not particularly limited. For example, from the perspective of making it easier to produce the cured product having the above-mentioned properties related to light transmission, the shear strength may be 65 MPa or less.

[0102] The shear strength of the cured product of the adhesive film can be appropriately adjusted within a range set by any combination of the above lower limit and upper limit. For example, in one embodiment, the shear strength is preferably 5 to 65 MPa, and can also be any range of 10 to 65 MPa, 15 to 65 MPa, 20 to 65 MPa, 30 to 65 MPa, and 40 to 65 MPa. However, the above range is only an example of the shear strength.

[0103] In this embodiment, the cured product of the adhesive film in the test piece for which the shear strength is specified is: a thermosetting adhesive film subjected to a heat treatment at 160° C. for 1 hour; or a cured product subjected to a heat treatment at an illumination of 230 mW / cm 2 , light intensity is 200mJ / cm 2 An energy ray cured product obtained by irradiating an energy ray curable adhesive film with energy rays under the conditions of.

[0104] The shear strength of the cured product of the adhesive film can be adjusted by adjusting the type or amount of the components contained in the adhesive film, etc. In particular, the shear strength can be adjusted in a wide range by adjusting the type or content of the polymer component (a), epoxy thermosetting resin (b), coupling agent (e) or crosslinking agent (f) described later in the components contained in the adhesive film.

[0105] The adhesive film may be composed of one layer (single layer) or two or more layers. When composed of multiple layers, the multiple layers may be the same as or different from each other, and the combination of the multiple layers is not particularly limited.

[0106] In addition, in this specification, not limited to adhesive films, "multiple layers may be the same as or different from each other" means "all layers may be the same, all layers may be different, or only some layers may be the same", and further, "multiple layers are different from each other" means "at least one of the constituent materials and thicknesses of each layer is different from each other".

[0107] The thickness of the adhesive film is not particularly limited, but is preferably 2 to 100 μm, more preferably 2 to 70 μm, and for example, 2 to 40 μm. By making the thickness of the adhesive film above the lower limit, the adhesive force of the adhesive film to the glass becomes higher. On the other hand, when the thickness of the adhesive film is below the upper limit, for example, the adhesive composition described later is more suitable for coating at a desired thickness, and the manufacturing suitability of the adhesive film is higher.

[0108] Here, the “thickness of the adhesive film” refers to the thickness of the entire adhesive film. For example, the thickness of an adhesive film composed of a plurality of layers refers to the total thickness of all the layers constituting the adhesive film.

[0109] The adhesive film can be formed using an adhesive composition containing its constituent materials. For example, the adhesive composition can be applied to the surface of the adhesive film to be formed, and dried as needed to form an adhesive film at the target site. A thermosetting adhesive film can be formed using a thermosetting adhesive composition, and an energy-ray-curable adhesive film can be formed using an energy-ray-curable adhesive composition.

[0110] The content ratio of the components that do not vaporize at room temperature in the adhesive composition is usually the same as the content ratio of the components in the adhesive film. In addition, in this specification, "room temperature" refers to a temperature that is not particularly cooled or heated, that is, a normal temperature, such as a temperature of 15 to 25°C.

[0111] The adhesive composition can be applied by a known method, for example, methods using various coaters such as an air knife coater, a blade coater, a rod coater, a gravure coater, a roll coater, a roll knife coater, a curtain coater, a die coater, a knife coater, a screen coater, a Meyer rod coater, and a kiss coater.

[0112] The drying conditions of the adhesive composition are not particularly limited, but when the adhesive composition contains a solvent described below, it is preferably dried by heating. For example, it is preferred to dry the adhesive composition containing a solvent at 70 to 130° C. for 10 seconds to 5 minutes.

[0113] Hereinafter, components contained in the adhesive film and the adhesive composition will be described in detail.

[0114] 《Thermosetting adhesive composition》

[0115] Examples of the thermosetting adhesive composition include a composition containing a polymer component (a) and an epoxy resin (b1) (abbreviated as "composition (I)" in this specification). Each component will be described below.

[0116] <Polymer component (a)>

[0117] The polymer component (a) can be regarded as a component formed by polymerization of a polymerizable compound, and is a high molecular weight component for imparting film-forming properties and flexibility to the adhesive film and for improving adhesion (adhesion) to an adhesive object (glass).

[0118] The polymer component (a) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0119] Examples of the polymer component (a) include acrylic resins, urethane resins, phenoxy resins, silicone resins, and saturated polyester resins, and acrylic resins are preferred.

[0120] Examples of the acrylic resin in the polymer component (a) include known acrylic polymers.

[0121] The weight average molecular weight (Mw) of the acrylic resin is preferably 10,000 to 2,000,000, more preferably 100,000 to 1,500,000, for example, 500,000 to 1,000,000. When the weight average molecular weight of the acrylic resin is within the above range, the adhesive strength between the adhesive film and the adherend can be easily adjusted to a preferred range.

[0122] On the other hand, by making the weight average molecular weight of the acrylic resin not less than the lower limit, the shape stability (stability over time during storage) of the adhesive film is improved. In addition, by making the weight average molecular weight of the acrylic resin not more than the upper limit, the adhesive film can easily follow the uneven surface of the adherend, and the generation of voids between the adherend and the adhesive film can be further suppressed.

[0123] In addition, in this specification, unless otherwise specified, "weight average molecular weight" means a polystyrene conversion value measured by gel permeation chromatography (GPC) method.

[0124] The glass transition temperature (Tg) of the acrylic resin is preferably -60 to 70°C, more preferably -30 to 50°C, for example, 0 to 30°C. By making the Tg of the acrylic resin above the lower limit, the adhesive force between the adhesive film and the adherend is suppressed, and it is easier to separate the glass chip with the adhesive film described above from the supporting sheet described later when picking up. By making the Tg of the acrylic resin below the upper limit, the adhesive force between the adhesive film and the adherend is improved.

[0125] When the acrylic resin has two or more structural units, the glass transition temperature (Tg) of the acrylic resin can be calculated using the Fox equation. As the Tg of the monomer from which the structural unit is derived, the value described in the Polymer Data Handbook or the Adhesive Handbook can be used.

[0126] Examples of the (meth)acrylate constituting the acrylic resin include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, and isononyl (meth)acrylate. , alkyl (meth)acrylates having a chain structure in which the alkyl group constituting the alkyl ester has 1 to 18 carbon atoms, such as decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate (myristyl (meth)acrylate), pentadecyl (meth)acrylate, hexadecyl (meth)acrylate (palmityl (meth)acrylate), heptadecyl (meth)acrylate, octadecyl (meth)acrylate (stearate (meth)acrylate), etc.;

[0127] Cycloalkyl (meth)acrylates such as isobornyl (meth)acrylate and dicyclopentyl (meth)acrylate;

[0128] Aralkyl (meth)acrylates such as benzyl (meth)acrylate;

[0129] Cycloalkenyl (meth)acrylates such as dicyclopentenyl (meth)acrylate;

[0130] Bicycloalkenyloxyalkyl (meth)acrylates such as dicyclopentenyloxyethyl (meth)acrylate;

[0131] (Meth)acrylimide;

[0132] (Meth)acrylates containing a glycidyl group, such as glycidyl (meth)acrylate;

[0133] (meth)acrylates containing hydroxy groups, such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate;

[0134] (Meth)acrylates containing a substituted amino group such as N-methylaminoethyl (meth)acrylate, etc. Here, the "substituted amino group" refers to a group having a structure in which one or two hydrogen atoms of an amino group are substituted with a group other than a hydrogen atom.

[0135] In addition, in this specification, "(meth)acrylic acid" is a concept including both "acrylic acid" and "methacrylic acid." Terms similar to (meth)acrylic acid are also the same.

[0136] The acrylic resin may be, for example, a resin obtained by copolymerizing, in addition to the (meth)acrylate, one or more monomers selected from (meth)acrylic acid, itaconic acid, vinyl acetate, acrylonitrile, styrene, and N-methylol acrylamide.

[0137] The monomers constituting the acrylic resin may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0138] In addition to the above-mentioned hydroxyl group, the acrylic resin may also have a functional group such as a vinyl group, a (meth)acryloyl group, an amino group, a carboxyl group, an isocyanate group, etc. that can be bonded to other compounds. The above-mentioned functional groups including the hydroxyl group of the acrylic resin may be bonded to other compounds via a crosslinking agent (f) described later, or may be directly bonded to other compounds without the crosslinking agent (f). By bonding the acrylic resin to other compounds via the functional groups, the cohesive force of the adhesive film is improved, and the physical stability of the adhesive film is improved.

[0139] In the acrylic resin, the ratio (content) of the amount of structural units derived from the glycidyl group-containing monomer to the total amount of structural units constituting the acrylic resin is preferably 25% by mass or less, for example, it can be any range of 15% by mass or less and 10% by mass or less. By making the ratio (content) below the upper limit, the compatibility and stability of the composition (I) are further improved. In addition, the glycidyl group-containing monomer refers to, for example, a monomer having a glycidyl group, such as the glycidyl group-containing (meth)acrylate.

[0140] In the acrylic resin, the lower limit of the ratio (content) of the amount of the structural unit derived from the glycidyl group-containing monomer relative to the total amount of the structural units constituting the acrylic resin is not particularly limited.

[0141] In the acrylic resin, the ratio (content) may be 0% by mass or more. For example, when it is 2% by mass or more, the effect of using the glycidyl group-containing monomer can be more significantly obtained.

[0142] In the acrylic resin, the ratio (content) of the amount of structural units derived from the glycidyl group-containing monomer relative to the total amount of structural units constituting the acrylic resin can be appropriately adjusted within the range set by arbitrarily combining the above lower limit and any upper limit. For example, in one embodiment, the ratio is preferably 0 to 25% by mass, for example, it can be any range of 0 to 15% by mass and 0 to 10% by mass. In addition, in one embodiment, the ratio is preferably 2 to 25% by mass, for example, it can be any range of 2 to 15% by mass and 2 to 10% by mass. However, the above range is only an example of the ratio.

[0143] In the present invention, as the polymer component (a), instead of using an acrylic resin, a thermoplastic resin other than an acrylic resin (hereinafter, sometimes simply referred to as a "thermoplastic resin") may be used alone, or an acrylic resin and a thermoplastic resin may be used simultaneously. By using the thermoplastic resin, it becomes easier to separate the glass chip with the adhesive film from the support sheet described later during pickup, and the adhesive film becomes easier to follow the concave-convex surface of the adherend, and the generation of gaps between the adherend and the adhesive film can be further suppressed.

[0144] The weight average molecular weight of the thermoplastic resin is preferably 1,000 to 100,000, more preferably 3,000 to 80,000.

[0145] The glass transition temperature (Tg) of the thermoplastic resin is -30 to 150°C, more preferably -20 to 120°C.

[0146] Examples of the thermoplastic resin include polyester, polyurethane, phenoxy resin, polybutene, polybutadiene, and polystyrene.

[0147] The thermoplastic resin contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0148] In the composition (I), the ratio of the content of the polymer component (a) to the total content of all components except the solvent (i.e., the ratio of the content of the polymer component (a) in the adhesive film to the total mass of the adhesive film) is preferably 5 to 80% by mass, regardless of the type of the polymer component (a), and may be, for example, any range of 5 to 50% by mass and 5 to 20% by mass, any range of 20 to 50% by mass and 30 to 50% by mass, or any range of 50 to 80% by mass and 60 to 80% by mass. By making the ratio of the content within the above range, the balance between the effect of using the polymer component (a) and the effect of using the components other than the polymer component (a) can be more widely adjusted.

[0149] In the composition (I) and the adhesive film, the content of the acrylic resin relative to the total content of the polymer component (a) is preferably 25 to 100% by mass, for example, it can be any range of 50 to 100% by mass, 70 to 100% by mass, and 90 to 100% by mass. By making the content ratio above the lower limit, the storage stability of the adhesive film is further improved.

[0150] <Epoxy resin (b1)>

[0151] As the epoxy resin (b1), known epoxy resins can be listed, for example, epoxy compounds with a functionality of two or more such as polyfunctional epoxy resins, biphenyl compounds, bisphenol A diglycidyl ether and its hydride, o-cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, biphenyl type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, and phenylene skeleton type epoxy resins can be listed.

[0152] As the epoxy resin (b1), an epoxy resin having an unsaturated hydrocarbon group can be used. The compatibility of the epoxy resin having an unsaturated hydrocarbon group with the acrylic resin described later is higher than the compatibility of the epoxy resin not having an unsaturated hydrocarbon group with the acrylic resin described later. Therefore, by using the epoxy resin (b1) having an unsaturated hydrocarbon group, the laminated structure of the cured product of the adhesive film and the glass can be maintained more stably.

[0153] Examples of epoxy resins having an unsaturated hydrocarbon group include compounds having a structure in which a portion of epoxy groups in a multifunctional epoxy resin is converted into a group having an unsaturated hydrocarbon group. Such compounds can be obtained, for example, by subjecting (meth)acrylic acid or a derivative thereof to an epoxy group by an addition reaction.

[0154] In addition, in this specification, unless otherwise specified, "derivative" refers to a compound having a structure in which one or more groups of the original compound are replaced by other groups (substituents). Here, "group" refers not only to an atomic group composed of multiple atoms bonded together, but also includes a single atom.

[0155] Examples of the epoxy resin having an unsaturated hydrocarbon group include compounds in which a group having an unsaturated hydrocarbon group is directly bonded to an aromatic ring or the like constituting the epoxy resin.

[0156] The unsaturated hydrocarbon group is a polymerizable unsaturated group, and specific examples thereof include an ethylene (vinyl) group, a 2-propenyl (allyl) group, a (meth)acryloyl group, a (meth)acrylamide group, and the like, preferably an acryloyl group.

[0157] The number average molecular weight of the epoxy resin (b1) is not particularly limited, but is preferably 300 to 30,000, more preferably 400 to 10,000, and particularly preferably 500 to 3,000 from the viewpoint of curability of the adhesive film and strength and heat resistance of the cured product of the adhesive film.

[0158] The epoxy equivalent of the epoxy resin (b1) is preferably 100 to 1000 g / eq, more preferably 150 to 650 g / eq, for example, 150 to 400 g / eq, or 400 to 650 g / eq.

[0159] The epoxy resin (b1) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0160] Commercially available products of epoxy resin (b1) include products containing acrylic resin particles (acrylic resin in particle form). In the present embodiment, by using epoxy resin (b1) that does not contain acrylic resin particles, for example, even when a component that easily aggregates acrylic resin particles by interaction with acrylic resin particles is used as polymer component (a), aggregation of such acrylic resin particles can be suppressed, thereby further improving the compatibility and stability of composition (I).

[0161] From the point of view of more clearly obtaining the above-mentioned effect, for example, in composition (I), the ratio of the content of acrylic resin microparticles to the total content of all components except the solvent (i.e., the ratio of the content of acrylic resin microparticles in the adhesive film to the total mass of the adhesive film) is regardless of the source of the acrylic resin microparticles and is preferably 0 to 5% by mass, more preferably 0 to 3% by mass.

[0162] In the composition (I) and the adhesive film, the content of the epoxy resin (b1) is preferably 15 to 660 parts by mass, more preferably 15 to 530 parts by mass, relative to 100 parts by mass of the polymer component (a). For example, it can be any range of 15 to 130 parts by mass and 15 to 65 parts by mass, or any range of 130 to 530 parts by mass and 330 to 530 parts by mass. By making the content of the epoxy resin (b1) within the above range, it is easier to adjust the adhesive force between the adhesive film and the support sheet described later.

[0163] In order to improve various physical properties of the adhesive film, the composition (I) and the adhesive film may contain other components that do not belong to the polymer component (a) and the epoxy resin (b1) as needed in addition to the polymer component (a) and the epoxy resin (b1).

[0164] Other components contained in the composition (I) and the adhesive film include, for example, thermosetting agents (b2), curing accelerators (c), fillers (d), coupling agents (e), crosslinking agents (f), energy-ray-curable resins (g), photopolymerization initiators (h), colorants (i), general additives (j), and the like.

[0165] <Thermosetting agent (b2)>

[0166] The thermosetting agent (b2) is a curing agent for the epoxy resin (b1). The combination of the epoxy resin (b1) and the thermosetting agent (b2) functions as an epoxy thermosetting resin (sometimes referred to as "epoxy thermosetting resin (b)" in this specification).

[0167] The epoxy thermosetting resin (b) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0168] As the thermosetting agent (b2), for example, there can be listed compounds having two or more functional groups that can react with epoxy groups in one molecule. As the functional group, for example, there can be listed phenolic hydroxyl group, alcoholic hydroxyl group, amino group, carboxyl group, group formed by dehydration of acid group, etc., preferably phenolic hydroxyl group, amino group or group formed by dehydration of acid group, more preferably phenolic hydroxyl group or amino group.

[0169] Examples of the phenolic curing agent having a phenolic hydroxyl group in the thermosetting agent (b2) include polyfunctional phenol resins, biphenol, novolac-type phenol resins, dicyclopentadiene-type phenol resins, and aralkyl-type phenol resins.

[0170] Among the thermosetting agents (b2), examples of amine-based curing agents having an amino group include dicyandiamide (DICY) and the like.

[0171] The heat curing agent (b2) may have an unsaturated hydrocarbon group.

[0172] Examples of the thermosetting agent (b2) having an unsaturated hydrocarbon group include a compound having a structure in which a part of the hydroxyl groups of a phenol resin is substituted by a group having an unsaturated hydrocarbon group; a compound having a structure in which a group having an unsaturated hydrocarbon group is directly bonded to an aromatic ring of a phenol resin; and the like.

[0173] The unsaturated hydrocarbon group in the thermosetting agent (b2) is the same as the unsaturated hydrocarbon group in the above-mentioned epoxy resin having an unsaturated hydrocarbon group.

[0174] When a phenolic curing agent is used as the thermosetting agent (b2), the thermosetting agent (b2) is preferably one having a high softening point or glass transition temperature from the viewpoint of facilitating adjustment of the adhesive strength of the adhesive film.

[0175] The number average molecular weight of the resin component such as the polyfunctional phenol resin, novolac phenol resin, dicyclopentadiene phenol resin, aralkyl phenol resin, etc. in the thermosetting agent (b2) is preferably 300 to 30,000, more preferably 400 to 10,000, and particularly preferably 500 to 3,000.

[0176] In the thermosetting agent (b2), the molecular weight of non-resin components such as biphenol and dicyandiamide is not particularly limited, but is preferably 60 to 500, for example.

[0177] The thermosetting agent (b2) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0178] When using a thermosetting agent (b2), in the composition (I) and the adhesive film, the content of the thermosetting agent (b2) is preferably 10 to 100 parts by mass, more preferably 10 to 60 parts by mass, relative to 100 parts by mass of the epoxy resin (b1), for example, it can be any range of 10 to 30 parts by mass and 10 to 20 parts by mass, or it can be any range of 30 to 60 parts by mass and 40 to 60 parts by mass. By making the content of the thermosetting agent (b2) above the lower limit, it is easier to cure the adhesive film. By making the content of the thermosetting agent (b2) below the upper limit, the moisture absorption rate of the adhesive film is reduced, and the laminated structure of the cured product of the adhesive film and the glass can be more stably maintained.

[0179] When a thermosetting agent (b2) is used, in the composition (I) and the adhesive film, the content of the epoxy thermosetting resin (b) (the total content of the epoxy resin (b1) and the thermosetting agent (b2)) is preferably 20 to 1000 parts by mass, more preferably 20 to 800 parts by mass, for example, it can be any range of 20 to 200 parts by mass and 20 to 100 parts by mass, or it can be any range of 200 to 800 parts by mass and 500 to 800 parts by mass. By making the content of the epoxy thermosetting resin (b) within the above range, it is easier to adjust the bonding force between the adhesive film and the support sheet described later.

[0180] <Curing Accelerator (c)>

[0181] The curing accelerator (c) is a component for adjusting the curing speed of the composition (I) and the adhesive film.

[0182] Preferred curing accelerators (c) include, for example, tertiary amines such as triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; imidazoles (imidazoles in which one or more hydrogen atoms are substituted by groups other than hydrogen atoms) such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole; organic phosphines (phosphines in which one or more hydrogen atoms are substituted by organic groups) such as tributylphosphine, diphenylphosphine, and triphenylphosphine; tetraphenylboron salts such as tetraphenylphosphoniumtetraphenylborate and triphenylphosphinetetraphenylborate; inclusion compounds having the above imidazoles as guest compounds, and the like.

[0183] The curing accelerator (c) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0184] When using a curing accelerator (c), regardless of whether a thermosetting agent (b2) is used, in the composition (I) and the adhesive film, the content of the curing accelerator (c) is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the total content of the epoxy resin (b1) and the thermosetting agent (b2). By making the content of the curing accelerator (c) above the lower limit, the effect of using the curing accelerator (c) can be more significantly obtained. By making the content of the curing accelerator (c) below the upper limit, for example, the effect of suppressing the high-polarity curing accelerator (c) from moving to the bonding interface side with the adherend in the adhesive film under high temperature and high humidity conditions and causing segregation becomes higher, and the laminated structure of the cured product of the adhesive film and the glass can be more stably maintained.

[0185] <Filling material (d)>

[0186] By making the adhesive film contain the filler (d), the thermal expansion coefficient of the adhesive film can be easily adjusted. By optimizing the thermal expansion coefficient of the object to which the adhesive film is attached, the laminated structure of the cured product of the adhesive film and the glass can be more stably maintained. In addition, by making the adhesive film contain the filler (d), the moisture absorption rate of the cured product of the adhesive film can be reduced and the heat dissipation can be improved.

[0187] The filler (d) may be any of an organic filler and an inorganic filler, but is preferably an inorganic filler.

[0188] Preferred inorganic fillers include, for example, powders of silica, alumina, talc, calcium carbonate, titanium dioxide, red iron oxide, silicon carbide, boron nitride, etc.; beads obtained by spheroidizing these inorganic fillers; surface-modified products of these inorganic fillers; single crystal fibers of these inorganic fillers; glass fibers, etc.

[0189] Among them, the inorganic filler is preferably silicon dioxide, aluminum oxide or surface-modified products thereof.

[0190] The average particle size of the filler (d) is not particularly limited, and can be, for example, 300 nm or less, preferably 200 nm or less, and can be any range of 10 to 200 nm, 10 to 150 nm, and 10 to 100 nm. By making the average particle size of the filler (d) above the lower limit, the effect of using the filler (d) can be more significantly obtained. By making the average particle size of the filler (d) below 200 nm, the cured product of the adhesive film can more easily achieve a light (850 nm) linear transmittance of 60% or more and a light (400 nm) linear transmittance of 40% or less.

[0191] In the present invention, unless otherwise specified, the "average particle size" refers to the particle size at which the cumulative value is 50% in the particle size distribution curve obtained by laser diffraction scattering method (D 50 ) value.

[0192] The filler (d) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0193] When filler (d) is used, in composition (I), the ratio of the content of filler (d) to the total content of all components except the solvent (i.e., the ratio of the content of filler (d) in the adhesive film to the total mass of the adhesive film) is preferably 5 to 60% by mass, more preferably 10 to 45% by mass, for example, 10 to 20% by mass, or 20 to 45% by mass. By making the content of filler (d) above the lower limit, it is easy to make the linear expansion coefficient of the adhesive film consistent with the linear expansion coefficient of the adherend, and it is easy to improve the adhesion between the adhesive film and the adherend. By making the content of filler (d) below the upper limit, the cured product of the adhesive film can more easily achieve a light (850nm) linear transmittance of more than 60% and a light (400nm) linear transmittance of less than 40%.

[0194] When filler (d) is used, in composition (I), the ratio of the content of filler (d) having an average particle size greater than 500 nm (average particle size (nm) > 500 nm) to the total content of all components other than the solvent (i.e., the ratio of the content of filler (d) having an average particle size greater than 500 nm in the adhesive film to the total mass of the adhesive film) is preferably 50% by mass or less, for example, any range of 30% by mass or less, 20% by mass or less, and 10% by mass or less. By making the ratio of the content below the upper limit, the cured product of the adhesive film can more easily achieve a light (850 nm) linear transmittance of 60% or more and a light (400 nm) linear transmittance of 40% or less. On the other hand, the ratio of the content is 0% or more.

[0195] <Coupling agent (e)>

[0196] By making the adhesive film contain the coupling agent (e), the adhesion and close adhesion to the adherend are improved. In addition, by making the adhesive film contain the coupling agent (e), the water resistance of its cured product is improved without impairing the heat resistance. The coupling agent (e) has a functional group that can react with an inorganic compound or an organic compound.

[0197] The coupling agent (e) is preferably a compound having a functional group reactive with a functional group possessed by the polymer component (a), the epoxy resin (b1), the thermosetting agent (b2), etc., and is more preferably a silane coupling agent.

[0198] Preferred silane coupling agents include, for example, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxymethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, 3- (2-aminoethylamino)propylmethyldiethoxysilane, 3-(phenylamino)propyltrimethoxysilane, 3-anilinopropyltrimethoxysilane, 3-ureapropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis(3-triethoxysilylpropyl)tetrasulfide, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriacetoxysilane, imidazole silane, oligomeric or polymeric organosiloxanes, etc.

[0199] The coupling agent (e) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0200] When using coupling agent (e), regardless of whether thermosetting agent (b2) is used, in composition (I) and adhesive film, the content of coupling agent (e) is preferably 0.03 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and particularly preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total content of polymer component (a), epoxy resin (b1) and thermosetting agent (b2). By making the content of coupling agent (e) above the lower limit, the dispersibility of filler (d) in the resin is improved, the adhesion of the adhesive film to the adherend is improved, etc., and the effect brought about by the use of coupling agent (e) can be more significantly obtained. By making the content of coupling agent (e) below the upper limit, the generation of outgas can be further suppressed.

[0201] <Crosslinking agent (f)>

[0202] When the above-mentioned acrylic resin or other compound having a functional group such as a vinyl group, a (meth)acryloyl group, an amino group, a hydroxyl group, a carboxyl group, an isocyanate group, etc. that can be bonded to other compounds is used as the polymer component (a), the composition (I) and the adhesive film may also contain a crosslinking agent (f) for bonding and crosslinking the functional group with other compounds. By crosslinking with the crosslinking agent (f), the initial adhesive force and cohesive force of the adhesive film can be adjusted.

[0203] Examples of the crosslinking agent (f) include organic polyisocyanate compounds, organic polyimide compounds, metal chelate crosslinking agents (crosslinking agents having a metal chelate structure), and aziridine crosslinking agents (crosslinking agents having an aziridine group).

[0204] As the organic polyisocyanate compound, for example, aromatic polyisocyanate compounds, aliphatic polyisocyanate compounds and alicyclic polyisocyanate compounds (hereinafter, these compounds are sometimes collectively referred to as "aromatic polyisocyanate compounds, etc."); trimers, isocyanurates and adducts of the aromatic polyisocyanate compounds, etc.; terminal isocyanate urethane prepolymers obtained by reacting the aromatic polyisocyanate compounds, etc. with polyol compounds, etc. The "adduct" refers to the reaction product of the aromatic polyisocyanate compound, aliphatic polyisocyanate compound or alicyclic polyisocyanate compound with a low molecular weight active hydrogen-containing compound such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane or castor oil. As an example of the adduct, the toluene diisocyanate trimer adduct of trimethylolpropane described later can be cited. In addition, the "terminal isocyanate urethane prepolymer" refers to a prepolymer having a urethane bond and an isocyanate group at the molecular end.

[0205] More specifically, examples of the organic polyisocyanate compound include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylene diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, 3-methyldiphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, dicyclohexylmethane-2,4'-diisocyanate, a compound obtained by adding one or more of toluene diisocyanate, hexamethylene diisocyanate and xylylene diisocyanate to all or part of the hydroxyl groups of a polyol such as trimethylolpropane, and lysine diisocyanate.

[0206] Examples of the organic polyimide compound include N,N′-diphenylmethane-4,4′-bis(1-aziridinecarboxamide), trimethylolpropane-tri-β-aziridine propionate, tetramethylolmethane-tri-β-aziridine propionate, and N,N′-toluene-2,4-bis(1-aziridinecarboxamide)triethylenemelamine.

[0207] When an organic polyisocyanate compound is used as the crosslinking agent (f), a hydroxyl-containing polymer is preferably used as the polymer component (a). When the crosslinking agent (f) has an isocyanate group and the polymer component (a) has a hydroxyl group, a crosslinking structure can be easily introduced into the adhesive film through the reaction between the crosslinking agent (f) and the polymer component (a).

[0208] The crosslinking agent (f) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0209] From the viewpoint of achieving a higher effect of suppressing the coloration of the adhesive film and its cured product, preferred crosslinking agents (f) include aliphatic polyisocyanate compounds, alicyclic polyisocyanate compounds, trimers, isocyanurates and adducts of aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds, and terminal isocyanate urethane prepolymers obtained by reacting aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds with polyol compounds.

[0210] The content of the crosslinking agent (f) is preferably 0 to 5 parts by mass, more preferably 0 to 3 parts by mass, and even more preferably 0 to 1 part by mass, relative to 100 parts by mass of the polymer component (a). It may also be 0 parts by mass, that is, the composition (I) and the adhesive film do not contain the crosslinking agent (f). When the content of the crosslinking agent (f) is below the above upper limit, the storage stability of the adhesive film becomes higher.

[0211] <Energy ray curable resin (g)>

[0212] By making the adhesive film contain the energy ray-curable resin (g), the characteristics of the adhesive film can be changed by irradiation with energy rays.

[0213] The energy-ray-curable resin (g) is a resin obtained by polymerizing (curing) an energy-ray-curable compound.

[0214] Examples of the energy-ray-curable compound include compounds having at least one polymerizable double bond in the molecule, and acrylate compounds having a (meth)acryloyl group are preferred.

[0215] Examples of the acrylate compounds include (meth)acrylates containing a chain aliphatic skeleton such as trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; (meth)acrylates containing a cyclic aliphatic skeleton such as dicyclopentyl di(meth)acrylate; polyalkylene glycol (meth)acrylates such as polyethylene glycol di(meth)acrylate; oligoester (meth)acrylates; urethane (meth)acrylate oligomers; epoxy-modified (meth)acrylates; polyether (meth)acrylates other than the polyalkylene glycol (meth)acrylates; itaconic acid oligomers, and the like.

[0216] The weight average molecular weight of the energy beam curable resin (g) is preferably 100 to 30,000, more preferably 300 to 10,000.

[0217] The energy-ray-curable resin (g) contained in the composition (I) may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0218] When an energy-ray curable resin (g) is used, the content of the energy-ray curable resin (g) in the composition (I) is preferably 1 to 95% by mass, for example, it can be any range of 1 to 50% by mass, 1 to 25% by mass and 1 to 10% by mass relative to the total mass of the composition (I).

[0219] <Photopolymerization Initiator (h)>

[0220] Regardless of whether or not the energy-ray-curable resin (g) is used, the composition (I) and the adhesive film may contain a photopolymerization initiator (h).

[0221] Examples of the photopolymerization initiator (h) include benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin benzoic acid methyl ester, and benzoin dimethyl ketal; acetophenone compounds such as acetophenone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, and 2,2-dimethoxy-1,2-diphenylethane-1-one; and acylphosphine oxide compounds such as phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. ; sulfides such as benzyl phenyl sulfide and tetramethylthiuram monosulfide; α-keto alcohol compounds such as 1-hydroxycyclohexyl phenyl ketone; azo compounds such as azobisisobutyronitrile; titanocene compounds such as titanocene; thioxanthone compounds such as thioxanthone; peroxide compounds; diketone compounds such as 2,3-butanedione; benzil; dibenzil; benzophenone; 2,4-diethylthioxanthone; 1,2-diphenylmethane; 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]acetone; quinone compounds such as 1-chloroanthraquinone and 2-chloroanthraquinone, etc.

[0222] Moreover, as a photopolymerization initiator (h), a photosensitizer, such as amine, etc., etc. are mentioned, for example.

[0223] The photopolymerization initiator (h) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0224] In the composition (I), the ratio of the content of the photopolymerization initiator (h) to the total mass of the composition (I) can be, for example, 0 to 15 mass parts. When using an energy-ray-curable resin (g), in the composition (I), the content of the photopolymerization initiator (h) is preferably 0 to 10 mass parts relative to 100 mass parts of the energy-ray-curable resin (g).

[0225] <Colorant (i)>

[0226] In the adhesive film and the cured product thereof, the colorant (i) is a component for adjusting not only the linear transmittance of light (850 nm) and the linear transmittance of light (400 nm), but also the linear transmittance of light of various wavelengths.

[0227] Examples of the colorant (i) include known colorants such as inorganic pigments, organic pigments, and organic dyes.

[0228] Examples of the organic pigments and organic dyes include amine pigments, cyanine pigments, merocyanine pigments, croconium pigments, squarylium pigments, azulenium pigments, polymethine pigments, naphthoquinone pigments, pyrylium pigments, phthalocyanine pigments, naphthalocyanine pigments, naphtholactam pigments, azo pigments, condensed coupler pigments, Nitrogen pigments, indigo pigments, perinone pigments, perylene pigments, dioxazine pigments, quinacridone pigments, isoindolinone pigments, quinophthalone pigments, pyrrole pigments, thioindigo pigments, metal complex pigments (metal complex salt dyes), dithiol metal complex pigments, indoxyl pigments, triarylmethane pigments, anthraquinone pigments, naphthol pigments, azomethine pigments, benzimidazolone pigments, pyranthrone pigments and threne pigments, etc.

[0229] Examples of the inorganic pigments include carbon black, cobalt pigments, iron pigments, chromium pigments, titanium pigments, vanadium pigments, zirconium pigments, molybdenum pigments, ruthenium pigments, platinum pigments, ITO (indium tin oxide) pigments, and ATO (antimony tin oxide) pigments.

[0230] The colorant (i) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When two or more kinds are used, the combination and ratio thereof may be arbitrarily selected.

[0231] When using a colorant (i), the content of the colorant (i) in the composition (I) and the adhesive film can be appropriately adjusted, for example, according to the type of the colorant (i). Generally, in the composition (I), the ratio of the content of the colorant (i) to the total content of all components other than the solvent (i.e., the ratio of the content of the colorant (i) in the adhesive film to the total mass of the adhesive film) is independent of the type of the colorant (i), preferably 0.01 to 10% by mass, more preferably 0.01 to 7.5% by mass, and particularly preferably 0.01 to 5% by mass. By making the ratio above the lower limit, the effect of using the colorant (i) can be more significantly obtained. By making the ratio below the upper limit, the light linear transmittance of the adhesive film and its cured product (for example, light (850nm) linear transmittance, light (400nm) linear transmittance) can be more easily adjusted.

[0232] <General Additives (j)>

[0233] The general additive (j) may be a known additive and may be selected as needed without particular limitation. Preferred general additives (j) include, for example, plasticizers, antistatic agents, antioxidants, gettering agents, defoamers, and leveling agents.

[0234] The general-purpose additive (j) contained in the composition (I) and the adhesive film may be one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0235] The content of the general-purpose additive (j) in the composition (I) and the adhesive film is not particularly limited and can be appropriately selected according to the type of the general-purpose additive (j), for example.

[0236] <Solvent>

[0237] It is preferred that the composition (I) further contains a solvent. The composition (I) containing a solvent has good handling properties.

[0238] The solvent is not particularly limited. Preferred solvents include, for example, hydrocarbons such as toluene and xylene; alcohols such as methanol, ethanol, 2-propanol, isobutanol (2-methylpropane-1-ol), and 1-butanol; esters such as ethyl acetate; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; amides (compounds containing amide bonds) such as dimethylformamide and N-methylpyrrolidone, etc.

[0239] The solvent contained in the composition (I) may be only one kind or two or more kinds. When there are two or more kinds, the combination and ratio thereof may be arbitrarily selected.

[0240] The solvent contained in the composition (I) is preferably methyl ethyl ketone or the like from the viewpoint that the components contained in the composition (I) can be mixed more uniformly.

[0241] 《Energy ray curable adhesive composition》

[0242] As the energy-ray-curable adhesive composition, for example, there can be listed a composition containing an energy-ray-curable component (sometimes abbreviated as "composition (II)" in this description), or a composition containing an energy-ray-curable component, a polymer not containing an energy-ray-curable group, and a photopolymerization initiator.

[0243] Examples of the energy-ray-curable component include resins having energy-ray-polymerizable unsaturated groups (energy-ray-polymerizable groups) such as acryloyl groups and groups that can react with other compounds such as glycidyl groups.

[0244] The epoxy resin (b1) in the composition (I) described above contains the energy-ray-curable component.

[0245] Examples of the polymer not containing an energy ray-curable group include acrylic polymers, phenoxy resins, urethane resins, polyesters, rubber-based resins, and acrylic urethane resins.

[0246] Among them, the polymer not containing an energy ray-curable group is preferably an acrylic polymer.

[0247] The polymer component (a) in the composition (I) described above includes a polymer not containing an energy ray-curable group.

[0248] Examples of the photopolymerization initiator include the same photopolymerization initiators as those mentioned above as the photopolymerization initiator (h) in the composition (I).

[0249] The content of the energy-ray curable component, the polymer not containing energy-ray curable groups, and the photopolymerization initiator in the composition (II) can be appropriately selected according to the types of these components and is not particularly limited. For example, when any of the energy-ray curable components, the polymer not containing energy-ray curable groups, and the photopolymerization initiator contains a component that belongs to any of the components contained in the composition (I), the content of the component in the composition (II) can be set to be the same as the content of the corresponding component in the composition (I).

[0250] The composition (II) may contain other components other than any of the energy-ray curable component, the polymer not containing an energy-ray curable group, and the photopolymerization initiator, as required.

[0251] Examples of the other components include one or more selected from the group consisting of epoxy resins, thermosetting agents, fillers, coupling agents, crosslinking agents, colorants, general additives, and solvents.

[0252] The epoxy resin, thermosetting agent, filler, coupling agent, cross-linking agent, colorant, general additive and solvent in composition (II) can be respectively listed as the same substances as the epoxy resin (b1), thermosetting agent (b2), filler (d), coupling agent (e), cross-linking agent (f), colorant (i), general additive (j) and solvent in composition (I).

[0253] The contents of the epoxy resin, thermosetting agent, filler, coupling agent, crosslinking agent, colorant, general additives and solvent in the composition (II) may be appropriately adjusted as required and are not particularly limited.

[0254] As an example of a preferable adhesive film among the adhesive films of this embodiment, the following can be mentioned:

[0255] An adhesive film, which is a curable adhesive film,

[0256] The adhesive film is used to bond two plates to each other, and the linear transmittance of the two plates to light with a wavelength of 800 to 1400 nm is 70% or more.

[0257] The cured product of the adhesive film has a linear transmittance of 60% or more to light with a wavelength of 850 nm.

[0258] The cured product of the adhesive film has a linear transmittance of 40% or less for light having a wavelength of 400 nm,

[0259] A test piece is prepared having a cured product of the adhesive film having a size of 2 mm×2 mm and a thickness of 20 μm, a first glass sheet having a thickness of 900 μm provided on the entire surface of one surface of the cured product, and a second glass sheet having a thickness of 350 μm provided on the entire surface of the other surface of the cured product, and the side surface of the cured product and the side surface of the second glass sheet are aligned. When a force is simultaneously applied to the aligned portion of the side surface of the cured product and the side surface of the second glass sheet in the test piece at a speed of 200 μm / s in a direction parallel to one surface of the cured product, the maximum value of the force applied until the cured product is broken or peeled off from the first glass sheet is 5 MPa or more,

[0260] The adhesive film contains a polymer component (a), an epoxy resin (b1) and a colorant (i).

[0261] In the adhesive film, the content of the polymer component (a) is 5 to 80% by mass relative to the total mass of the adhesive film.

[0262] The content of the epoxy resin (b1) in the adhesive film is 15 to 660 parts by mass relative to 100 parts by mass of the polymer component (a).

[0263] In the adhesive film, the content of the colorant (i) is 0.01 to 10% by mass based on the total mass of the adhesive film.

[0264] As another example of a preferred adhesive film among the adhesive films of this embodiment, the following can be mentioned:

[0265] An adhesive film, which is a curable adhesive film,

[0266] The adhesive film is used to bond two plates to each other, and the linear transmittance of the two plates to light with a wavelength of 800 to 1400 nm is 70% or more.

[0267] The cured product of the adhesive film has a linear transmittance of 60% or more to light with a wavelength of 850 nm.

[0268] The cured product of the adhesive film has a linear transmittance of 40% or less for light having a wavelength of 400 nm,

[0269] A test piece is prepared having a cured product of the adhesive film having a size of 2 mm×2 mm and a thickness of 20 μm, a first glass sheet having a thickness of 900 μm provided on the entire surface of one surface of the cured product, and a second glass sheet having a thickness of 350 μm provided on the entire surface of the other surface of the cured product, and the side surface of the cured product and the side surface of the second glass sheet are aligned. When a force is simultaneously applied to the aligned portion of the side surface of the cured product and the side surface of the second glass sheet in the test piece at a speed of 200 μm / s in a direction parallel to one surface of the cured product, the maximum value of the force applied until the cured product is broken or peeled off from the first glass sheet is 5 MPa or more,

[0270] The adhesive film contains a polymer component (a), an epoxy resin (b1) and a colorant (i).

[0271] In the adhesive film, the content of the polymer component (a) is 5 to 80% by mass relative to the total mass of the adhesive film.

[0272] The content of the epoxy resin (b1) in the adhesive film is 15 to 660 parts by mass relative to 100 parts by mass of the polymer component (a).

[0273] In the adhesive film, the content of the colorant (i) is 0.01 to 10% by mass relative to the total mass of the adhesive film.

[0274] The adhesive film further contains a thermosetting agent (b2) and a coupling agent (e), and contains a filler (d) or a cross-linking agent (f).

[0275] As another example of a preferred adhesive film among the adhesive films of the present embodiment, there can be mentioned:

[0276] An adhesive film, which is a curable adhesive film,

[0277] The adhesive film is used to bond two plates to each other, and the linear transmittance of the two plates to light with a wavelength of 800 to 1400 nm is 70% or more.

[0278] The cured product of the adhesive film has a linear transmittance of 60% or more to light with a wavelength of 850 nm.

[0279] The cured product of the adhesive film has a linear transmittance of 40% or less for light having a wavelength of 400 nm,

[0280] A test piece is prepared having a cured product of the adhesive film having a size of 2 mm×2 mm and a thickness of 20 μm, a first glass sheet having a thickness of 900 μm provided on the entire surface of one surface of the cured product, and a second glass sheet having a thickness of 350 μm provided on the entire surface of the other surface of the cured product, and the side surface of the cured product and the side surface of the second glass sheet are aligned. When a force is simultaneously applied to the aligned portion of the side surface of the cured product and the side surface of the second glass sheet in the test piece at a speed of 200 μm / s in a direction parallel to one surface of the cured product, the maximum value of the force applied until the cured product is broken or peeled off from the first glass sheet is 5 MPa or more,

[0281] The adhesive film contains a polymer component (a), an epoxy resin (b1) and a colorant (i).

[0282] The polymer component (a) does not contain an energy-ray-curable group,

[0283] The epoxy resin (b1) has an energy ray polymerizable unsaturated group and a group that can react with other compounds.

[0284] In the adhesive film, the content of the polymer component (a) is 5 to 80% by mass relative to the total mass of the adhesive film.

[0285] The content of the epoxy resin (b1) in the adhesive film is 15 to 660 parts by mass relative to 100 parts by mass of the polymer component (a).

[0286] In the adhesive film, the content of the colorant (i) is 0.01 to 10% by mass relative to the total mass of the adhesive film.

[0287] The adhesive film further contains a photopolymerization initiator.

[0288] 《Method for preparing adhesive composition》

[0289] The adhesive composition (thermosetting adhesive composition, energy ray-curable adhesive composition) can be obtained by blending the respective components constituting the composition.

[0290] The order of adding the components when blending them is not particularly limited, and two or more components may be added simultaneously.

[0291] When a solvent is used, the solvent may be mixed with any blending component other than the solvent and the blending component may be diluted in advance before use, or the solvent and the blending components may be mixed without diluting any blending component other than the solvent in advance.

[0292] When blending, the method for mixing the components is not particularly limited, and may be appropriately selected from known methods such as a method of mixing by rotating a stirring bar or a stirring blade, a method of mixing using a mixer, and a method of mixing by applying ultrasonic waves.

[0293] The temperature and time for adding and mixing the components are not particularly limited as long as the components do not deteriorate, and may be appropriately adjusted. However, the temperature is preferably 15 to 30°C.

[0294] ◇Adhesive composite sheet and method of using the same

[0295] An adhesive composite sheet according to one embodiment of the present invention includes a support sheet, and the adhesive film according to one embodiment of the present invention described above is provided on one surface of the support sheet.

[0296] The adhesive composite sheet of this embodiment can be used as a dicing wafer for dividing glass into glass chips by dicing to produce the glass chips with adhesive films described above. That is, the support sheet in the adhesive composite sheet can be used as a dicing wafer.

[0297] Supporting film

[0298] The support sheet may be composed of one layer (single layer) or more than two layers. When the support sheet is composed of multiple layers, the constituent materials and thicknesses of the multiple layers may be the same or different from each other, and there is no particular limitation on the combination of the multiple layers as long as the effect of the present invention is not impaired.

[0299] Preferred examples of the support sheet include a support sheet consisting only of a base material, and a support sheet having a base material and an adhesive layer provided on one surface of the base material.

[0300] When the supporting sheet has the base material and the adhesive layer, in the adhesive composite sheet, the adhesive layer is disposed between the base material and the adhesive film.

[0301] The support sheet consisting only of a substrate is suitable as a carrier sheet or a cutting sheet. The adhesive composite sheet having such a support sheet consisting only of a substrate is used in the following manner: the surface of the adhesive film opposite to the side having the support sheet (i.e., the substrate) (sometimes referred to as the "first surface" in this specification) is attached to one surface of the glass.

[0302] When a support sheet consisting only of a base material is used, a pressure-sensitive adhesive composite sheet can be produced at low cost.

[0303] On the other hand, the support sheet having a substrate and an adhesive layer is suitable as a dicing sheet. The adhesive composite sheet having such a support sheet is also used in the following manner: the surface (first surface) of the adhesive film opposite to the side having the support sheet is attached to one surface of the glass.

[0304] When a support sheet having a substrate and an adhesive layer is used, the adhesive force or adhesion between the support sheet and the adhesive film can be easily adjusted in the adhesive composite sheet.

[0305] The method of using the adhesive composite sheet will be described in detail later.

[0306] Hereinafter, each layer constituting the supporting sheet will be described.

[0307] <Base Material>

[0308] The substrate is in a sheet or film shape, and examples of its constituent material include various resins.

[0309] Examples of the resin include polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE); polyolefins other than polyethylenes such as polypropylene, polybutene, polybutadiene, polymethylpentene, and norbornene resins; ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylate copolymers, and ethylene-norbornene copolymers (copolymers obtained using ethylene as a monomer); vinyl chloride resins such as polyvinyl chloride and vinyl chloride copolymers; Polyesters such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene isophthalate, polyethylene 2,6-naphthalate, and fully aromatic polyesters in which all structural units have aromatic cyclic groups; copolymers of two or more of the above polyesters; poly(meth)acrylates; polyurethanes; polyurethane acrylates; polyimides; polyamides; polycarbonates; fluororesins; polyacetals; modified polyphenylene ethers; polyphenylene sulfides; polysulfones; polyether ketones, etc.

[0310] In addition, examples of the resin include polymer alloys such as a mixture of the polyester and other resins. The amount of the resin other than polyester in the polymer alloy of the polyester and other resins is preferably relatively small.

[0311] In addition, examples of the resin include crosslinked resins obtained by crosslinking one or more of the resins listed above; and modified resins such as ionomers using one or more of the resins listed above.

[0312] The resin constituting the substrate may be only one type or two or more types. When there are two or more types, the combination and ratio thereof may be arbitrarily selected.

[0313] The substrate may consist of one layer (single layer) or two or more layers. When the substrate consists of multiple layers, the multiple layers may be the same as or different from each other, and the combination of the multiple layers is not particularly limited.

[0314] The thickness of the substrate is preferably 50 to 300 μm, more preferably 60 to 150 μm. By making the thickness of the substrate within the above range, the flexibility of the adhesive composite sheet and the adhesion to glass components (for example, the glass wafer, cover glass, inner glass plate, etc. described above) are further improved.

[0315] Here, the “thickness of the substrate” refers to the thickness of the entire substrate. For example, the thickness of a substrate composed of a plurality of layers refers to the total thickness of all the layers constituting the substrate.

[0316] In addition to the main constituent materials such as the resin, the base material may contain various known additives such as a filler, a colorant, an antistatic agent, an antioxidant, an organic lubricant, a catalyst, and a softener (plasticizer).

[0317] The substrate can be transparent or opaque, can be colored as required, and can also be vapor-deposited with other layers.

[0318] In order to improve the adhesion between the substrate and the layer provided on the substrate (for example, an adhesive layer, an adhesive film, etc.), the substrate surface can be subjected to a roughening treatment based on sandblasting, solvent treatment, etc.; an oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone / ultraviolet irradiation treatment, flame treatment, chromic acid treatment, hot air treatment, etc.

[0319] Furthermore, the surface of the substrate may be subjected to a primer treatment.

[0320] Furthermore, the substrate may have an antistatic coating, a layer for preventing the substrate from adhering to other sheets when the adhesive composite sheets are stacked and stored, or a layer for preventing the substrate from adhering to an adsorption table.

[0321] Furthermore, the substrate may have a release-treated layer on the surface. The release-treated layer may be formed by performing a release treatment on the surface of the substrate using various known release agents.

[0322] Furthermore, by making the base material contain a component (for example, a resin) within a specific range, at least one surface of the base material may have adhesiveness.

[0323] The substrate can be produced by a known method. For example, the substrate containing the resin can be produced by molding a resin composition containing the above resin.

[0324] <Adhesive layer>

[0325] The adhesive layer is in a sheet or film shape and contains an adhesive.

[0326] Examples of the adhesive include adhesive resins such as acrylic resins, urethane resins, rubber-based resins, silicone resins, epoxy-based resins, polyvinyl ethers, polycarbonates, and ester-based resins.

[0327] In this specification, "adhesive resin" includes resins having adhesive properties and resins having adhesive properties. For example, the adhesive resin includes not only resins having adhesive properties per se, but also resins that exhibit adhesive properties by being used together with other components such as additives, or resins that exhibit adhesive properties due to the presence of triggers such as heat or water.

[0328] The adhesive layer may consist of one layer (single layer) or two or more layers. When the adhesive layer consists of multiple layers, the multiple layers may be the same or different from each other, and the combination of the multiple layers is not particularly limited.

[0329] The thickness of the adhesive layer is not particularly limited, but is preferably 1 to 100 μm, more preferably 1 to 60 μm, and particularly preferably 1 to 30 μm.

[0330] Here, “the thickness of the adhesive layer” refers to the thickness of the entire adhesive layer. For example, the thickness of an adhesive layer composed of a plurality of layers refers to the total thickness of all the layers constituting the adhesive layer.

[0331] The adhesive layer may be an adhesive layer formed using an energy-ray-curable adhesive or an adhesive layer formed using a non-energy-ray-curable adhesive. That is, the adhesive layer may be either energy-ray-curable or non-energy-ray-curable. The energy-ray-curable adhesive layer can easily adjust the physical properties before and after curing.

[0332] The adhesive layer can be formed using an adhesive composition containing an adhesive. For example, the adhesive composition can be applied to the surface of the adhesive layer and dried as needed to form the adhesive layer at the target site. The content ratio of the components that do not vaporize at room temperature in the adhesive composition is usually the same as the content ratio of the components in the adhesive layer.

[0333] The adhesive composition can be applied by the same method as the above-mentioned pressure-sensitive adhesive composition.

[0334] When the adhesive layer is energy-ray-curable, the energy-ray-curable adhesive composition may include, for example, the following adhesive compositions: an adhesive composition (I-1) containing a non-energy-ray-curable adhesive resin (I-1a) (hereinafter, sometimes abbreviated as "adhesive resin (I-1a)") and an energy-ray-curable compound; an adhesive composition (I-2) containing an energy-ray-curable adhesive resin (I-2a) (hereinafter, sometimes abbreviated as "adhesive resin (I-2a)") having an unsaturated group introduced into the side chain of the adhesive resin (I-1a); and an adhesive composition (I-3) containing the adhesive resin (I-2a) and an energy-ray-curable compound.

[0335] When the adhesive layer is non-energy ray-curable, examples of the non-energy ray-curable adhesive composition include an adhesive composition (I-4) containing the above-mentioned adhesive resin (I-1a).

[0336] The adhesive compositions (I-1) to (I-4) and the like can be prepared by the same method as the above-mentioned adhesive composition except that the mixed components are different.

[0337] Figure 3 This is a cross-sectional view schematically showing an example of a pressure-sensitive adhesive composite sheet according to an embodiment of the present invention.

[0338] The adhesive composite sheet 101 shown here has a support sheet 10 and an adhesive film 13 on a first surface 10 a of the support sheet 10 .

[0339] The support sheet 10 is composed only of the substrate 11, that is, the adhesive composite sheet 101 has a structure in which an adhesive film 13 is laminated on one surface (sometimes referred to as the "first surface" in this specification) 11a of the substrate 11. The first surface 11a of the substrate 11 is the same as the first surface 10a of the support sheet 10.

[0340] The adhesive composite sheet 101 further includes a release film 15 on a surface (sometimes referred to as a “first surface” in this specification) 13 a of the adhesive film 13 that is opposite to the substrate 11 side.

[0341] Release film 15 and Figure 1 The first release film 151 or the second release film 152 shown are the same.

[0342] The release film 15 is an optional structure, and the adhesive composite sheet 101 does not necessarily have to include the release film 15 .

[0343] The first surface 13 a of the adhesive film 13 and the surface (sometimes referred to as “second surface” in this specification) 13 b opposite to the first surface 13 a are both surfaces to be attached to glass.

[0344] Next, a method of using the adhesive composite sheet 101 will be described.

[0345] First, in the adhesive composite sheet 101 , after removing the release film 15 from the adhesive film 13 , one surface of a glass wafer is attached to the first surface 13 a of the adhesive film 13 .

[0346] Next, the glass wafer is divided into glass chips, and the adhesive film 13 is cut into chip sizes to form glass chips with adhesive films, and a collection of glass chips with adhesive films is produced, wherein the collection of glass chips with adhesive films is in a state where a plurality (a large number) of the above-mentioned glass chips with adhesive films are held on the support sheet 10. As a method for dividing (cutting) the glass wafer into glass chips, for example, blade cutting using a blade can be cited, but it is not limited to this, and all known methods for singulating a wafer can be applied.

[0347] Next, the glass chip with the adhesive film is separated and picked up from the support sheet 10 (substrate 11) by a known method, and the picked up glass chip with the adhesive film is attached to the glass component through the exposed surface of the adhesive film (i.e., the second surface 13b of the adhesive film 13 after cutting).

[0348] The intermediate laminate structure is obtained in the above manner, and the intermediate laminate structure has a structure in which glass is attached to both surfaces (first surface 13a, second surface 13b) of the cut adhesive film 13. The glass chip can be used as the cover glass described above, and the inner glass plate described above can be cited as the glass member.

[0349] In this intermediate laminate structure, the adhesive film 13 after dicing is further cured, and the glasses (that is, the glass chip and the glass member) are more firmly bonded together by the cured product.

[0350] Thus, a target laminated structure having a structure in which glass is laminated on both surfaces of the cured product of the diced adhesive film 13 is obtained.

[0351] In this laminated structure, the cured product of the adhesive film 13 allows targeted infrared light to be transmitted from one glass to the other glass (for example, from the cover glass to the inner glass plate) with high linear transmittance, while transmission of non-target visible light can be suppressed.

[0352] Figure 4This is a cross-sectional view schematically showing another example of the adhesive composite sheet according to one embodiment of the present invention.

[0353] The adhesive composite sheet 102 shown here is the same as the adhesive composite sheet 101 except that it has a support sheet 20 instead of the support sheet 10. The support sheet 20 has a substrate 11 and an adhesive layer 12 provided on a first surface 11a of the substrate 11. In the adhesive composite sheet 102, the adhesive layer 12 is arranged between the substrate 11 and the adhesive film 13, that is, the adhesive composite sheet 102 is formed by sequentially stacking the substrate 11, the adhesive layer 12 and the adhesive film 13 along their thickness direction. The surface 12a of the adhesive layer 12 on the adhesive film 13 side (sometimes referred to as the "first surface" in this specification) is the same as the first surface 20a of the support sheet 20.

[0354] The adhesive composite sheet 102 further includes a release film 15 on the first surface 13a of the adhesive film 13. In the adhesive composite sheet 102, the release film 15 is an optional configuration.

[0355] Next, a method of using the adhesive composite sheet 102 will be described.

[0356] First, a glass wafer is attached to the adhesive film 13 in the adhesive composite sheet 102 using the same method as when using the adhesive composite sheet 101 to form a glass chip with an adhesive film, thereby producing an assembly of glass chips with an adhesive film, wherein the assembly of glass chips with an adhesive film is in a state where a plurality (a large number) of glass chips with an adhesive film are maintained on the support sheet 20, more specifically on the first surface 12a of the adhesive layer 12.

[0357] Next, the glass chip with the adhesive film is separated and picked up from the support sheet 20 (adhesive layer 12) by a known method. At this time, when the adhesive layer is energy-ray-curable, it is easier to pick up the glass chip with the adhesive film from the support sheet 20 (adhesive layer 12) by curing the adhesive layer. Thereafter, an intermediate stacked structure is obtained by the same method as when the adhesive composite sheet 101 is used, and the intermediate stacked structure has a structure in which glass is attached to both sides (the first side 13a and the second side 13b) of the adhesive film 13. The intermediate stacked structure obtained here is the same as when the adhesive composite sheet 101 is used. Therefore, thereafter, the same target stacked structure as when the adhesive composite sheet 101 is used is obtained by the same method as when the adhesive composite sheet 101 is used.

[0358] The adhesive composite sheet of this embodiment is not limited to Figure 3-4 The adhesive composite sheet shown in the figure may be changed or deleted without impairing the effect of the present invention. Figure 3-4The adhesive composite sheet of the partial configuration shown may be an adhesive composite sheet having another configuration added to the adhesive composite sheet described above.

[0359] For example, Figure 3-4 The adhesive composite sheet shown may also be provided with other structures that are not any of the substrate, adhesive layer, adhesive film, and release film at any position. Such other structures include, for example: a sheet-like or film-like intermediate layer disposed between any two of the above four layers (substrate, adhesive layer, adhesive film, release film); an annular clamp adhesive layer disposed along the edge of one surface of a support sheet (e.g., substrate or adhesive layer). The clamp adhesive layer is used to fix the support sheet to a fixing fixture such as an annular frame.

[0360] In addition, Figure 3-4 In the adhesive composite sheet shown, a partial gap may be generated between the release film and the layer in direct contact with the release film.

[0361] In addition, Figure 3-4 In the above-described bonded composite sheet, the size and shape of each layer can be arbitrarily adjusted according to the purpose.

[0362] So far, the adhesive composite sheet and the method of using the same have been described. However, not only the above-mentioned pre-made adhesive composite sheet can be used, but also an adhesive film in a state without a support sheet can be used to attach the glass to the adhesive film. In this case, after attaching the glass to the adhesive film, the support sheet or cutting sheet is attached to the exposed surface of the adhesive film on the opposite side to the side to which the glass is attached, thereby obtaining the same cutting object as when the pre-made adhesive composite sheet is used.

[0363] ◇Method for manufacturing bonded composite sheet

[0364] The adhesive composite sheet can be produced by laminating the above-mentioned layers in a corresponding positional relationship and adjusting the shapes of a part or all of the layers as necessary. The formation method of each layer is the formation method described above.

[0365] For example, when manufacturing a supporting sheet, when laminating an adhesive layer on a substrate, the adhesive composition may be applied on the substrate and dried as necessary.

[0366] In addition, the adhesive layer can also be laminated on the substrate by applying an adhesive composition on a release film and drying it as needed to form an adhesive layer on the release film in advance, and laminating the exposed surface of the adhesive layer to one surface of the substrate. In this case, the adhesive composition is preferably applied to the release-treated surface of the release film.

[0367] Although the case of laminating an adhesive layer on a substrate has been cited as an example, the above method can also be applied to the case of laminating other structures such as the intermediate layer described above on a substrate, and the case of laminating the adhesive film on a substrate. When laminating the adhesive film, the adhesive composition is used.

[0368] On the other hand, for example, when a new layer (hereinafter referred to as the "second layer") is further laminated on the outermost layer (hereinafter referred to as the "first layer") already laminated on the substrate, the second layer is formed on the release film in advance using a composition for forming the second layer, and the exposed surface of the formed second layer opposite to the side in contact with the release film is bonded to the exposed surface of the first layer on the substrate, thereby forming a continuous two-layer laminated structure (in other words, a laminated structure of the first layer and the second layer). At this time, it is preferred to apply the composition on the release-treated surface of the release film. After the laminated structure is formed, the release film can be removed as needed. When the second layer is the adhesive film, the adhesive composition is used as the composition for forming the second layer.

[0369] In this way, the layers constituting the adhesive composite sheet other than the substrate can be laminated by pre-forming on a release film and laminating on the surface of the target layer. Therefore, the adhesive composite sheet can be manufactured by appropriately selecting the layers to be used in such a process as required.

[0370] In addition, the adhesive composite sheet is usually stored in a state where a release film is attached to the surface of the outermost layer (e.g., adhesive film) on the opposite side of the support sheet. Therefore, by applying the adhesive composition or the like on the release film (preferably on the release-treated surface thereof) and drying it as needed, a layer constituting the outermost layer is formed on the release film in advance, and the remaining layers are stacked on the exposed surface of the layer opposite to the side in contact with the release film by any of the above methods, and the release film is maintained without removing the release film and attached to the release film, an adhesive composite sheet with a release film can be obtained.

[0371] Example

[0372] The present invention will be described in more detail below by way of specific examples, but the present invention is not limited to the following examples.

[0373] <Single>

[0374] The formal names of monomers abbreviated in the present Examples and Comparative Examples are shown below.

[0375] MA: Methyl acrylate

[0376] EA: Ethyl acrylate

[0377] BA: n-butyl acrylate

[0378] HEA: 2-Hydroxyethyl Acrylate

[0379] GMA: Glycidyl Methacrylate

[0380] AN: Acrylonitrile

[0381] <Raw materials for preparing adhesive composition>

[0382] The raw materials used for preparing the adhesive composition in the present example and the comparative example are shown below.

[0383] [Polymer component (a)]

[0384] (a)-1: Acrylic resin obtained by copolymerization of BA (40 parts by mass), EA (25 parts by mass), AN (30 parts by mass) and GMA (5 parts by mass) (weight average molecular weight 700,000, glass transition temperature 14° C.)

[0385] (a)-2: Acrylic resin (weight average molecular weight 800,000, glass transition temperature 9° C.) obtained by copolymerization (living polymerization) of MA (95 parts by mass) and HEA (5 parts by mass)

[0386] (a)-3: Acrylic resin obtained by copolymerization (living polymerization) of MA (85 parts by mass) and HEA (15 parts by mass) (weight average molecular weight 800,000, glass transition temperature 6° C.)

[0387] (a)-4: Acrylic resin obtained by copolymerization of BA (55 parts by mass), MA (10 parts by mass), GMA (20 parts by mass) and HEA (15 parts by mass) (weight average molecular weight 800,000, glass transition temperature -28°C)

[0388] [Epoxy resin (b1)]

[0389] (b1)-1: Bisphenol A type epoxy resin ("jER828" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 184 to 194 g / eq)

[0390] (b1)-2: Cresol novolac type epoxy resin ("EOCN-1020" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 191 to 207 g / eq)

[0391] (b1)-3: Liquid epoxy resin containing a triazine skeleton ("TEPIC-PAS B22" manufactured by Nissan Chemical Corporation, epoxy equivalent 180 to 200 g / eq)

[0392] (b1)-4: Cresol novolac type epoxy resin to which an acryl group is added ("CNA147" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 518 g / eq, number average molecular weight 2100, unsaturated group content equal to epoxy group content)

[0393] (b1)-5: A mixture of a liquid bisphenol A epoxy resin and acrylic rubber particles ("BPA328" manufactured by NIPPON SHOKUBAICO., LTD., epoxy equivalent 235 g / eq)

[0394] (b1)-6: solid bisphenol A type epoxy resin ("jER1055" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 800 to 900 g / eq)

[0395] [Thermosetting agent (b2)]

[0396] (b2)-1: o-cresol novolac type phenol resin ("BRG556" manufactured by SHOWA DENKO KK)

[0397] (b2)-2: Aralkyl phenol resin ("HE100C-10" manufactured by AIR WATER INC.)

[0398] (b2)-3: dicyandiamide (thermally active latent epoxy resin curing agent, "ADEKAHARDENER EH-3636AS" manufactured by ADEKA CORPORATION, active hydrogen equivalent 21 g / eq)

[0399] [Curing accelerator (c)]

[0400] (c)-1: 2-phenyl-4,5-dihydroxymethylimidazole ("CUREZOL 2PHZ-PW" manufactured by SHIKOKU CHEMICALS CORPORATION)

[0401] [Filling material (d)]

[0402] (d)-1: Spherical silica modified with epoxy groups ("ADMANANOYA050C-MKK" manufactured by Admatechs, average particle size 50 nm)

[0403] (d)-2: Spherical silica modified with epoxy groups ("ADMANANOYA050C-MKK" manufactured by Admatechs, average particle size 500 nm)

[0404] (d)-3: Spherical silica treated with methacryl silane ("YA050C-MJE" manufactured by Admatechs, average particle size 50 nm)

[0405] [Coupling agent (e)]

[0406] (e)-1: 3-glycidyloxypropyldiethoxysilane ("KBE-402" manufactured by Shin-Etsu Silicone Co., Ltd., silane coupling agent)

[0407] [Crosslinking agent (f)]

[0408] (f)-1: Trimethylolpropane-toluene diisocyanate trimer adduct ("CORONATE L" manufactured by TOSOH CORPORATION, solid content concentration 70 mass %)

[0409] [Energy ray curable resin (g)]

[0410] (g)-1: tricyclodecane dimethylol diacrylate ("KAYARA DR-684" manufactured by Nippon Kayaku Co., Ltd., ultraviolet curable resin, molecular weight 304)

[0411] [Photopolymerization initiator (h)]

[0412] (h)-1: 1-Hydroxycyclohexylphenylketone ("IRGACURE (registered trademark) 184" manufactured by BASF)

[0413] [Colorant (i)]

[0414] (i)-1: Organic black pigment ("6733 Black" manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.)

[0415] [General additives (j)]

[0416] (j)-1: Bis(decyl)pentaerythritol diphosphite ("JPE-10" manufactured by JOHOKU CHEMICAL CO., LTD., antioxidant)

[0417] (j)-2: Silicone oil ("XF-42-334" manufactured by Momentive Performance Materials Japan LLC.)

[0418] [Example 1]

[0419] 《Manufacturing of adhesive films》

[0420] <Preparation of Adhesive Composition>

[0421] A polymer component (a)-1 (9.8 parts by mass), an epoxy resin (b1)-1 (25.3 parts by mass), an epoxy resin (b1)-2 (22.5 parts by mass), a thermosetting agent (b2)-1 (24.6 parts by mass), a curing accelerator (c)-1 (0.2 parts by mass), a filler (d)-1 (14.6 parts by mass), a coupling agent (e)-1 (1 part by mass) and a colorant (i)-1 (2 parts by mass) are dissolved or dispersed in methyl ethyl ketone, and stirred at 23° C. to obtain an adhesive composition having a total concentration of all the above components except methyl ethyl ketone of 50% by mass. The amounts of the components except methyl ethyl ketone shown here are all amounts of the target product excluding the solvent component.

[0422] <Manufacturing of Adhesive Film>

[0423] A release film ("SP-PET381031" manufactured by LINTEC CORPORATION, thickness 38 μm, first release film) obtained by subjecting one side of a polyethylene terephthalate (PET) film to a release treatment by silicone treatment was used, and the above-obtained adhesive composition was applied to the release-treated surface of the first release film, and heated and dried at 100° C. for 5 minutes to form a curable adhesive film with a thickness of 20 μm.

[0424] Next, the release-treated surface of the same release film (second release film) as above is bonded to the exposed surface of the adhesive film opposite to the release film side, thereby obtaining a laminated film in which the first release film, the adhesive film and the second release film are sequentially laminated in their thickness direction.

[0425] <Manufacturing of Adhesive Composite Sheet>

[0426] The second release film is removed from the laminated film obtained above, and a polyolefin substrate (FUNCRARE LLD, thickness 80 μm) is adhered to the exposed surface of the adhesive film thus produced, thereby obtaining an adhesive composite sheet with a release film, in which the substrate (i.e., the supporting sheet), the adhesive film and the release film (i.e., the first release film) are stacked in sequence along their thickness direction.

[0427] 《Evaluation of adhesive films》

[0428] <Measurement of Light Linear Transmittance of Adhesive Film>

[0429] The light linear transmittance of a slide glass (thickness: 900 μm) was measured using a spectrophotometer (“UV-3101PC” manufactured by Shimadzu Corporation).

[0430] Next, the second release film was removed from the laminated film obtained above, and the exposed surface of the adhesive film was bonded to one surface of the slide glass, thereby preparing a first test piece.

[0431] Next, the spectrophotometer was used to perform baseline correction based on the measurement results of the linear transmittance of the light of the slide glass obtained above, and light was directly received from the slide glass side of the first test piece, thereby measuring the linear transmittance of the light of the adhesive film in the first test piece obtained above. The measurement results of the linear transmittance of light (400nm) and the linear transmittance of light (850nm) of the adhesive film obtained at this time are shown in Table 1.

[0432] <Measurement of Light Linear Transmittance of Cured Adhesive Film>

[0433] The first test piece after measuring the light linear transmittance of the adhesive film was heat-treated at 160° C. for 1 hour to thermally cure the adhesive film, thereby preparing a second test piece.

[0434] Next, the light was directly received from the slide glass side of the second test piece in the same manner as the first test piece, thereby measuring the light linear transmittance of the cured product (thermocured product) of the adhesive film in the second test piece. The measurement results of the light (400nm) linear transmittance and light (850nm) linear transmittance of the cured product obtained at this time are shown in Table 1.

[0435] <Measurement of Light Linear Transmittance of Additional Heated Object>

[0436] The second test piece after the measurement of the light linear transmittance of the cured product was further subjected to a heat treatment at 175° C. for 5 hours, and the cured product was additionally heated to obtain a third test piece.

[0437] Next, the linear transmittance of light of the additionally heated object in the third test piece was measured by directly receiving light from the slide glass side of the third test piece in the same manner as the first test piece. The measurement results of the linear transmittance of light (850 nm) of the additionally heated object obtained at this time are shown in Table 1.

[0438] <Method for measuring shear strength of cured adhesive film>

[0439] The adhesive layer of a dicing tape ("Adwill D-210" manufactured by LINTEC CORPORATION) was bonded to the exposed surface of the polyolefin substrate in the obtained adhesive composite sheet opposite to the adhesive film side to obtain a laminate of the dicing tape and the adhesive composite sheet.

[0440] Next, the first release film was removed from the laminate, and the exposed surface of the adhesive film was bonded to one surface of a glass sheet (diameter 150 nm, thickness 350 μm).

[0441] Next, a cutting device ("DFD6362" manufactured by DISCO Corporation) is used to cut the glass sheet together with the adhesive film, thereby obtaining an assembly of glass chips with adhesive films, in which a plurality (a large number) of glass chips with adhesive films are maintained on a support sheet (i.e., a substrate). At this time, "R07-SDC400-BB300-100 (54×0.23A×40)" manufactured by DISCO Corporation is used as a cutting blade, and the cutting blade is used to cut into the surface of the adhesive film side of the support sheet at a depth of 20 μm under the conditions of a rotation speed of 50,000 rpm, a feed speed of 5 mm / s, and a height of 0.185 mm, thereby cutting the support sheet to obtain glass chips with adhesive films of a size of 2 mm×2 mm.

[0442] Next, a glass chip with an adhesive film is picked up from the assembly of glass chips with adhesive film obtained above, and the entire exposed surface of its adhesive film (the surface opposite to the glass chip side) is bonded to one surface (i.e., a solid chip) of the same slide glass (thickness 900 μm) as above, thereby obtaining a stacked product in which the slide glass (equivalent to the first glass sheet), the adhesive film and the glass chip (equivalent to the second glass sheet) are stacked in sequence along their thickness direction.

[0443] Furthermore, the adhesive film in the stack was heated at 160°C for 1 hour to be thermally cured, thereby obtaining a fourth test piece consisting of a slide glass (equivalent to the first glass piece), a cured adhesive film and a glass chip (equivalent to the second glass piece) stacked in sequence along their thickness direction.

[0444] Next, force was applied simultaneously to the aligned portions of the side of the cured product of the adhesive film of the fourth test piece and the side of the glass chip at a speed of 200 μm / s in a direction parallel to one surface of the cured product. At this time, a stainless steel plate-shaped pressing device was used as an extrusion device for applying force, so that the extrusion device did not contact the glass slide. In addition, the maximum value of the force applied to the cured product when it was damaged or peeled off from the glass slide was measured, and the measured value was used as the shear strength of the cured product. The results are shown in Table 1.

[0445] <Evaluation of Infrared Transmittance of Cured Adhesive Film>

[0446] The laminated film obtained above was heat-treated at 160° C. for 1 hour to thermally cure the adhesive film, thereby obtaining a cured product (thermocured product) similar to the cured product of the adhesive film in the second test piece.

[0447] The second release film was removed from the cured product, and the exposed surface of the cured product was attached to a TV remote controller ("CT-90372" manufactured by TOSHIBA CORPORATION) so as to cover the infrared emitter of the TV remote controller. Furthermore, the first release film was removed from the cured product.

[0448] Next, in this state, the remote controller was operated, and five observers were asked to observe through the solidified object using a digital camera whether infrared rays emitted during the operation could be confirmed. The number of the five observers who could confirm infrared rays is shown in Table 1. In Table 1, for example, "4 / 5" means that four of the five observers confirmed infrared rays.

[0449] <Evaluation of infrared transmittance of additionally heated object>

[0450] The laminated film obtained above was heated at 160°C for 1 hour to thermally cure the adhesive film, and the thermally cured laminated film was further heated at 175°C for 5 hours to additionally heat the cured adhesive film, thereby obtaining the same additionally heated product as the additionally heated product in the third test piece.

[0451] The infrared transmittance of the additionally heated product obtained above was evaluated in the same manner as for the cured product.

[0452] 《Manufacturing of adhesive films and adhesive composite sheets, and evaluation of adhesive films》

[0453] [Examples 2 to 4, Comparative Examples 1 to 4]

[0454] Adhesive films and adhesive composite sheets were prepared and evaluated by the same method as in Example 1, except that either or both of the types and amounts of the ingredients blended when preparing the adhesive composition were changed so that the types and amounts of the ingredients contained in the adhesive composition were as shown in Table 1. The total concentration of all ingredients in the adhesive composition except methyl ethyl ketone was 35% by mass in Examples 2 to 4, Comparative Examples 2 and 4, and 50% by mass in Comparative Examples 1 and 3. The results are shown in Table 1.

[0455] In addition, "-" in the column of contained components in Table 1 means that the adhesive composition does not contain the component.

[0456] [Example 5, Comparative Example 5]

[0457] A curable adhesive film and an adhesive composite sheet were prepared in the same manner as in Example 1, except that the types and amounts of the ingredients blended when preparing the adhesive composition were changed so that the types and amounts of the ingredients contained in the adhesive composition were as shown in Table 1. The total concentration of all ingredients in the adhesive composition except methyl ethyl ketone was 35% by mass.

[0458] And, at an illumination of 230mW / cm 2 , light intensity is 200mJ / cm 2 The adhesive film and the adhesive composite sheet were evaluated in the same manner as in Example 1 except that the adhesive film was irradiated with ultraviolet rays once under the conditions of 100° C. to cure the adhesive film with energy rays, instead of heat-curing the adhesive film at 160° C. for 1 hour to prepare a cured product of the adhesive film. The results are shown in Table 1.

[0459] [Table 1]

[0460]

[0461] [Table 2]

[0462]

[0463] It is clear from the above results that in Examples 1 to 5, the light (850 nm) linear transmittance of the cured product of the adhesive film is 67% or more (67 to 80%), and the linear transmittance of the cured product of the adhesive film to infrared rays is sufficiently high. This reflects that in these Examples, the light (850 nm) linear transmittance of the adhesive film is 68% or more (68 to 93%), which is sufficiently high.

[0464] In Examples 1 to 5, the cured products and the additionally heated products of the adhesive films all had good infrared transmittance, which is consistent with the above-mentioned result of the linear transmittance of light (850 nm).

[0465] In addition, in Examples 1 to 5, the light (400nm) linear transmittance of the cured product of the adhesive film was 34% or less (4 to 34%), and the linear transmittance of the cured product of the adhesive film to visible light was sufficiently low. This reflects that in these Examples, the light (400nm) linear transmittance of the adhesive film was 35% or less (13 to 35%), which was sufficiently low.

[0466] Furthermore, in Examples 1 to 5, the shear strength of the cured product of the adhesive film was 6 MPa or more (6 to 58 MPa), and the adhesive force of the cured product to glass was sufficiently high.

[0467] Based on the above results, it can be confirmed that regardless of the curability (thermosetting, energy ray curing) of the adhesive films of Examples 1 to 5, they are suitable for stably forming the following device for a sensor with a cover glass: a device that allows infrared rays as the detection object to be transmitted and suppresses the transmission of visible light other than the target.

[0468] In Examples 1 to 5, the light linear transmittance (850 nm) of the additionally heated product was 65% or more (65 to 79%), which was still sufficiently high, and the practicality of the cured product was obviously high.

[0469] In contrast, in Comparative Examples 1 and 3, the light (850 nm) linear transmittance of the cured product of the adhesive film was 46% or less (42 to 46%), and the linear transmittance of the cured product of the adhesive film to infrared rays was low. This reflects that in these comparative examples, the light (850 nm) linear transmittance of the adhesive film was 68% or less (46 to 68%), which was low.

[0470] In Comparative Examples 1 and 3, the cured products and the additionally heated products of the adhesive films were both poor in infrared transmittance, which is consistent with the above-mentioned result of the linear transmittance of light (850 nm).

[0471] On the other hand, in Comparative Examples 2, 4, and 5, the light (400 nm) linear transmittance of the cured product of the adhesive film was 54% or more (54 to 93%), and the linear transmittance of the cured product of the adhesive film to visible light was high. This reflects that in these comparative examples, the light (400 nm) linear transmittance of the adhesive film was 55% or more (55 to 94%), which was significantly high.

[0472] From the above results, it was confirmed that the adhesive films of Comparative Examples 1 to 5 were not suitable for use in sensors having a cover glass, regardless of the curability (thermosetting property, energy ray curing property).

[0473] Industrial Applicability

[0474] The present invention can be used to form a device for a sensor having a cover glass, which transmits infrared light to be detected and suppresses transmission of visible light other than the target.

Claims

1. An adhesive film, which is a thermosetting adhesive film, The adhesive film is used to bond two plates to each other, and the linear transmittance of the two plates to light with a wavelength of 800nm ​​to 1400nm is 70% or more. The heat-cured adhesive film has a linear transmittance of 60% or more to light with a wavelength of 850 nm. The heat-cured adhesive film has a linear transmittance of 40% or less for light having a wavelength of 400 nm. The adhesive film contains a polymer component (a) and an epoxy resin (b1), wherein the polymer component (a) is an acrylic resin and does not contain an energy ray-curable group. A test piece is prepared by preparing a thermosetting article having the adhesive film having a size of 2 mm×2 mm and a thickness of 20 μm, a first glass sheet having a thickness of 900 μm provided on the entire surface of one surface of the thermosetting article, and a second glass sheet having a thickness of 350 μm provided on the entire surface of the other surface of the thermosetting article, and by aligning the side surface of the thermosetting article with the side surface of the second glass sheet. When force is simultaneously applied to the aligned portion of the side surface of the thermosetting article and the side surface of the second glass sheet in the test piece at a speed of 200 μm / s in a direction parallel to one surface of the thermosetting article, the maximum value of the force applied until the thermosetting article is broken or the thermosetting article is peeled off from the first glass sheet is 5 MPa or more. 2 . The adhesive film according to claim 1 , wherein a heat-cured product of the adhesive film obtained by heating the heat-cured product at 175° C. for 5 hours has a linear transmittance of 50% or more for light having a wavelength of 850 nm. 3 . An adhesive composite sheet comprising a support sheet and the adhesive film according to claim 1 or 2 on one surface of the support sheet.

4. The adhesive composite sheet according to claim 3, wherein: The support sheet comprises a substrate and an adhesive layer disposed on one surface of the substrate. The adhesive layer is disposed between the substrate and the adhesive film.